Electrolyte

By using electrolyte compositions with nonaqueous solvents and performance additives, the toxicity and corrosiveness of the existing electrolyte compositions are solved, and the lightweight and high-performance operation of the battery is achieved, reducing environmental impact.

CN119790504APending Publication Date: 2025-04-08FARADION LTD

Patent Information

Application Number
CN202380060864.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-08-23
Filing Date
2023-05-05
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In the prior art, the electrolyte composition of metal ion batteries and anode-free sodium batteries needs to contain metal ion salts, which leads to toxicity and corrosive problems, and the density of the electrolyte is high, affecting the lightweight and environmental friendliness of the battery.

Method used

An electrolyte composition containing a non-aqueous solvent and performance additives is used, and the metal-containing salt has a concentration of 0 mol/kg to ≤0.2 mol/kg. This composition is used as an electrolyte to achieve stable operation and performance improvement of the battery.

Benefits of technology

It reduces the toxicity and corrosiveness of the electrolyte, reduces the total weight of the battery, improves the circulation and rate performance of the battery, and does not increase the use of fossil fuels, thereby reducing environmental impact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119790504A_ABST
    Figure CN119790504A_ABST
Patent Text Reader

Abstract

The present invention relates to the use of a composition comprising a solvent system comprising a first component comprising one or more non-aqueous solvents and a second component comprising one or more performance additives as an electrolyte. Apparatuses and methods including the electrolyte compositions are also disclosed.
Need to check novelty before this filing date? Find Prior Art

Description

Field of the Invention

[0001] The present invention relates to a composition and its use as an electrolyte (ie, "electrolyte composition"), preferably as an electrolyte in an electrochemical cell. Also disclosed are methods, devices and apparatus for using the electrolyte composition. Background of the Invention

[0003] Metal ion batteries (e.g., alkali metal ion batteries such as sodium ion batteries; potassium ion batteries; lithium ion batteries) are reusable secondary batteries that include an anode (negative electrode), a cathode (positive electrode), and an electrolyte material, and are capable of storing energy. Metal ion batteries include an active material layer coated on a current collector foil to form a cathode, and a similar arrangement exists for the corresponding anode. The cathode and anode are physically separated by a separator that allows ions to flow in a liquid electrolyte medium that is uniformly present in the battery and wets the entire cathode, anode, and separator. When a metal ion battery is charged, the Na + (or K + , Li + ) ions shuttle from the cathode active material and embed into the anode active material (electrons flow through the external circuit), and the reverse process occurs during discharge (sodium ions are removed from the anode active material and embedded into the cathode active material as electrons flow through the external circuit, doing useful work).

[0004] "Anode-free sodium battery" refers to a battery in which the working principle of the anode-free sodium battery involves the extraction / insertion of sodium metal cations (Na + ) and the plating / stripping of sodium metal (Na) on the anode current collector. This operating principle is different from the metal-ion batteries discussed above, where the operating principle of metal-ion batteries involves the extraction / insertion of metal cations (e.g., Na) at the cathode active material. + , K + , Li + ) and the extraction / intercalation of metal cations (e.g., Na + , K + , Li + ).

[0005] One area that requires more attention is the development of suitable electrolyte compositions, particularly for use in metal ion batteries and / or anode-free sodium batteries.

[0006] The main purpose of the electrolyte composition in both metal ion batteries and anode-free sodium batteries is to provide transport pathways for positively electroactive metal ions while prohibiting electron transfer through the same medium. Therefore, the importance of the electrolyte composition should not be overlooked as it is largely the key to the battery life and determining the actual performance that can be achieved by the battery, such as in terms of capacity, rate capability, safety, etc.

[0007] Until now, conventional theory has held that in order for an electrolyte composition in a metal ion battery to function, it must contain a metal ion salt. In support of this, applicants cite Huggins (Advanced Batteries: Materials Science Aspects, Springer, 2008), Chapter 14, page 322, Section 14B.3, “Lithium Salts,” which states that “[t]he solvents [are] required to function as electrolytes in lithium batteries. must Contains lithium salts".

[0008] It is also generally accepted in the battery community that the ionic conductivity (mS / cm) of the liquid electrolyte is important in determining the kinetic response of the battery. In support of this, the applicant cites Chayambuka et al. (“An experimental and modelling study of sodium-ion battery electrolytes”, Journal of Power Sources, 516, 2021, 230658).

[0009] The document demonstrates, using model experiments, that when the concentration of NaPF6 salt in a 1:1 mixed ethylene carbonate:propylene carbonate electrolyte is zero, the conductivity (mS / cm) of the electrolyte is predicted to be zero.

[0010] In fact, Chayambuka et al. Figure 3 a shows that in dilute electrolyte solutions, the ionic conductivity actually increases with the sodium salt concentration until it reaches about 1 mol kg -1 The optimal concentration.

[0011] Similarly, Logan et al. (“A critical evaluation of advanced electrolyte models”, J. Electrochem. Soc., 165, 2018) Figure 4 and Figure 6 To reiterate Chayambuka's teaching, zero concentration of both lithium and sodium salts will produce zero electrolyte ionic conductivity.

[0012] Thus, the general teaching at present is that an electrolyte composition substantially free of one or more metal-containing salts will result in infinite polarization of the liquid electrolyte regardless of the cell C-rate. As a result, the electrolyte composition will have zero ionic conductivity on its surface, thus prohibiting charging / discharging of the cell; i.e., it is expected that the cell / battery will not function at all.

[0013] The use of batteries, and therefore the use of electrolytes, is becoming increasingly common, particularly in stationary applications and in automotive applications (e.g. electric vehicles). However, due to certain suspected environmental issues, including the generation of toxic and corrosive gases associated with the use of non-renewable fossil fuels, there is an increasing desire to use batteries (possibly in combination with renewable fuels), and therefore to use electrolyte compositions in such batteries that have low or even zero levels of toxicity and / or corrosiveness.

[0014]

[0006] Therefore, there is a need for low or no toxicity and / or low or no corrosion electrolyte compositions that provide batteries that are alternatives to fossil fuels and are considered to be safer for the environment.

[0015] In addition, electric vehicle manufacturers, for example, are under increasing pressure to make their vehicles lighter to improve efficiency and performance. It is also desirable to make batteries that are lighter and easier to install in stationary applications. Therefore, there is a need for batteries and, therefore, electrolyte compositions that provide alternatives to existing electrolyte compositions and are considered to be lighter (i.e., have a lower density) alternatives to existing electrolyte compositions.

[0016] However, it is generally believed that a suitable electrolyte composition must satisfy a series of attributes including:

[0017] • Chemical stability – must not react during battery operation, including reactions within the electrolyte itself or with the separators, electrodes, current collectors, or packaging materials used;

[0018] • Electrochemical stability – there must be a wide electrochemical stability window, i.e. a large interval between the high and low onset potentials for decomposition by oxidation or reduction;

[0019] • Thermal stability – the electrolyte composition must not decompose or chemically degrade during normal cell operation and at operating temperatures;

[0020] • Physical properties – the electrolyte composition must be a liquid, so its melting and boiling points must be well above the internal operating temperature of the battery;

[0021] • High ionic conductivity and low electronic conductivity are necessary to maintain battery operation and minimize battery self-discharge via metal ion transport, respectively;

[0022] • based on sustainable chemistry, i.e. using abundant elements and made via low-impact synthesis (energy, pollution, etc.); and

[0023] • Cost-effective manufacturing.

[0024] With respect to usage efficiency, it is important to note that a loss in cycling or rate performance of an electrolyte composition may have secondary environmental impacts through increased fossil fuel usage resulting from increased demand for electrical energy.

[0025] Furthermore, it is generally believed that low or no toxicity and / or low or no corrosive and / or low density electrolyte compositions are desirable to be effective in batteries without requiring significant changes to conventional battery manufacturing techniques.

[0026] It is therefore an object of the present invention to mitigate or eliminate one or more of the above mentioned disadvantages of the prior art. SUMMARY OF THE INVENTION

[0028] The present invention achieves these objects by providing: the use of a composition comprising a solvent system as an electrolyte, the solvent system comprising:

[0029] A first component comprising one or more non-aqueous solvents;

[0030] a second component comprising one or more performance additives; and

[0031] Wherein, the electrolyte composition comprises a metal salt at a concentration of 0 mol / kg to ≤0.2 mol / kg.

[0032] The terms "electrolyte" and "electrolyte composition" referred to herein should be considered equivalent to each other and can be used interchangeably.

[0033] The concentration of the metal salt is conveniently expressed as its mass molar concentration in the solvent system; that is, the total number of moles of the metal salt per 1 kg or 1000 g of the solvent system (i.e., the combined weight of the first component and the second component). Optionally, the concentration of the metal salt is 0 mol / kg to ≤ 0.1 mol / kg.

[0034] Alternatively, concentrations disclosed herein as "M" (molarity) relate to the total number of moles of metal-containing salt per liter of solvent system.

[0035] Typically, the electrolyte composition is substantially free of one or more metal-containing salts. Since the electrolyte composition according to the present invention substantially excludes metal-containing salts, the toxicity and / or corrosiveness of the composition is generally considered to be suppressed compared to electrolyte compositions having metal-containing salts. In fact, typical metal-containing salts are generally present in a molar concentration of about 0.5 to 2 m, such as 5-35% by weight, preferably 7 to 32% by weight, of the total amount of the electrolyte composition, and common metal-containing salts in sodium ion batteries are toxic and / or corrosive, as described below:

[0036] Sodium hexafluorophosphate (NaPF6):

[0037] Corrosive / irritant hazard: Skin corrosion, Category 1B, H314

[0038] Toxicity Hazards: Oral – Category 4, H302; Inhalation, Category 4, H332; Skin, Category 4, H312.

[0039] Information obtained from Sigma Aldrich Safety Data Sheet Version 6.2; NaPF6; Product No. 208051.

[0040] Sodium Perchlorate (NaClO4)

[0041] Corrosive / Irritation Hazard: Eye Irritation, Category 2, H319

[0042] Toxicity Hazards: Oral – Category 4, H302, Specific Organ Toxicity – Repeated Exposure, Category 2, Thyroid, H373

[0043] Information obtained from Sigma Aldrich Safety Data Sheet Version 6.5; NaClO4; Product No. 906700.

[0044] Sodium bis(trifluoromethanesulfonyl)imide (NaTFSI)

[0045] Corrosive / Irritation Hazards: Skin Corrosion: Category 1B, H314, Eye Irritation: Category 1, H318, May cause respiratory irritation, H335.

[0046] Information obtained from Solvionic Safety Data Sheet, 8th edition; NaTFSI; Product No. M1108C.

[0047] Furthermore, in the absence of a metal-containing salt (which is solid at room temperature), a person skilled in the art will appreciate that the density of the electrolyte composition according to the present invention will be lower than that of an electrolyte composition containing a metal-containing salt, since the latter will have a limited amount of solid powder dissolved in the solvent mixture, and it is well known that the density of a solid is generally higher than that of a liquid. In fact, Monti et al., Phys. Chem. Chem. Phys., 2020, 22, 22768-22777 Figure 4 c and 4d clearly show that the density of the electrolyte increases with increasing concentration of the metal-containing salt, up to about 11% between 0.3 M and 2 M for either the NaTFSI or NaPF6 systems. The inventors also observed similar benefits in terms of lower density of electrolytes made according to the present invention.

[0048] Therefore, since the electrolyte compositions of the present invention are believed to be lighter (i.e., have a lower density) than existing metal salt-containing electrolyte compositions, this makes the electrolyte compositions of the present invention particularly ideal in metal ion batteries and / or anode-free sodium batteries for mobile (e.g., automotive) or stationary applications.

[0049] As demonstrated by the experimental performance data disclosed herein, the cycle and / or rate performance of the electrolyte composition of the present invention is considered to be similar or improved compared to existing metal salt-containing electrolyte compositions. Therefore, the electrolyte composition of the present invention is not considered to cause secondary environmental impacts by increasing the use of fossil fuels. In addition, eliminating the need for salts not only significantly reduces manufacturing costs, but also improves the overall simplicity of battery functionality.

[0050] As disclosed herein, the electrolyte compositions of the present invention are generally substantially free of one or more metal-containing salts. However, to the extent that the electrolyte compositions of the present invention contain one or more metal-containing salts, the amounts contained therein were previously believed not to produce any practical benefit in the cycling performance of practical electrochemical cells.

[0051] In one embodiment, the conductivity of the electrolyte composition at 25° C. may be less than 3 mS / cm, preferably less than 2.5 mS / cm, more preferably less than 2 mS / cm. Alternatively, the conductivity range at 30° C. may be less than 5 mS / cm.

[0052] In one embodiment, the electrolyte composition of the present invention may contain water in an amount of no more than about 500 ppm. In one embodiment, the electrolyte composition of the present invention may contain water in an amount of about 100 ppm to 500 ppm. In some embodiments, the electrolyte composition of the present invention is substantially free of water.

[0053] As used herein, the phrase "metal-containing salt" refers to a metal salt that can impart ionic conductivity to the electrolyte composition.

[0054] The second component of the solvent system may comprise or consist essentially of one or more performance additives. The one or more performance additives as the second component of the solvent system are preferably selected from sulfur-containing compounds, boron-containing compounds and surfactants.

[0055] One or more performance additives may be present as a second component of the solvent system in an amount of >0.5% to ≤10% by weight of the solvent system.

[0056] One or more of these performance additives as a second component of the solvent system can achieve the formation of a stable cathode-electrolyte interface (CEI) on the cathode and / or a stable solid-electrolyte interface (SEI) on the anode, or bring other benefits, such as improving the wetting of the electrolyte on the separator and / or electrode materials by reducing the surface tension and / or surface adsorption effects of the solvent system, which can effectively form an artificial SEI / CEI layer, which in turn leads to advantages such as increased Coulombic efficiency and increased cathode discharge capacity.

[0057] Preferably, the one or more performance additives are selected from sulfur-containing compounds and are present as the second component of the solvent system in an amount of >0% to ≤10% by weight of the solvent system.

[0058] For the avoidance of any doubt, the phrase "the weight of the solvent system" as used herein refers to the weight of the first component of the solvent system combined with the weight of the second component of the solvent system.

[0059] The sulfur-containing compound may be present as a second component of the solvent system in an amount of >0.1% to ≤10% by weight of the solvent system, preferably ≥0.2% to ≤9% by weight of the solvent system, and more preferably ≥0.3% to ≤5%. Optionally, the sulfur-containing compound may be present as a second component of the solvent system in an amount of about 1%, about 2%, or about 5% by weight of the solvent system. As a second component, an amount of about 5% by weight of the solvent system is highly preferred.

[0060] More preferably, the one or more performance additives are selected from boron-containing compounds, which are present as the second component of the solvent system in an amount of >0% to ≤10% by weight of the solvent system.

[0061] The boron-containing compound may be present as a second component of the solvent system in an amount of >0.1% to ≤10% by weight of the solvent system, preferably ≥0.2% to ≤9% by weight of the solvent system, and more preferably ≥0.3% to ≤5%. Optionally, the boron-containing compound may be present as a second component of the solvent system in an amount of about 1%, about 2%, or about 5% by weight of the solvent system. As a second component, an amount of about 1% or about 5% by weight of the solvent system is highly preferred.

[0062] Alternatively, the one or more performance additives are selected from surfactants, which are present as the second component of the solvent system in an amount of >0% to ≤10% by weight of the solvent system.

[0063] The surfactant may be present as a second component of the solvent system in an amount of >0.1% to ≤10% by weight of the solvent system, preferably ≥0.2% to ≤9% by weight of the solvent system, and more preferably ≥0.3% to ≤5%. Optionally, the surfactant may be present as a second component of the solvent system in an amount of about 1%, about 2%, or about 5% by weight of the solvent system. As a second component, an amount of about 1% by weight of the solvent system is highly preferred.

[0064] The second component of the solvent system may comprise or consist essentially of two or more performance additives. The two or more performance additives may be present as the second component of the solvent system in an amount of >0.5% to ≤10% by weight of the solvent system.

[0065] The two or more performance additives as the second component of the solvent system may comprise a mixture of a boron-containing compound and a surfactant. That is, one or more boron-containing compounds may be mixed with one or more surfactants to provide a mixture of two or more performance additives.

[0066] The two or more performance additives as the second component of the solvent system may comprise a mixture of a boron-containing compound in an amount of ≥0.5% to <10% by weight of the solvent system and a surfactant in an amount of ≥0.5% to <10% by weight of the solvent system. Optionally, the total amount of the two or more performance additives as the second component of the solvent system does not exceed about 10% by weight based on the weight of the solvent system.

[0067] The two or more performance additives as the second component of the solvent system may comprise a mixture of a boron-containing compound in an amount of ≥1% to <5% by weight of the solvent system and a surfactant in an amount of ≥1% to <5% by weight of the solvent system. Optionally, the total amount of the two or more performance additives as the second component of the solvent system does not exceed about 5% by weight based on the weight of the solvent system.

[0068] Alternatively, the two or more performance additives as the second component of the solvent system can comprise a mixture of sulfur-containing compounds and surfactants. That is, one or more sulfur-containing compounds can be mixed with one or more surfactants to provide a mixture of two or more performance additives.

[0069] The two or more performance additives as the second component of the solvent system may comprise a mixture of a sulfur-containing compound in an amount of ≥0.5% to <10% by weight of the solvent system and a surfactant in an amount of ≥0.5% to <10% by weight of the solvent system. Optionally, the total amount of the two or more performance additives as the second component of the solvent system is preferably no more than about 10% by weight based on the weight of the solvent system.

[0070] The two or more performance additives as the second component of the solvent system may comprise a mixture of a sulfur-containing compound in an amount of ≥1% to <5% by weight of the solvent system and a surfactant in an amount of ≥1% to <5% by weight of the solvent system. Optionally, the total amount of the two or more performance additives as the second component of the solvent system does not exceed about 5% by weight based on the weight of the solvent system.

[0071] The second component of the solvent system may comprise or consist essentially of three or more performance additives. The three or more performance additives may be present as the second component of the solvent system in an amount of >0.5% to ≤10% by weight of the solvent system.

[0072] The three or more performance additives of the second component of the solvent system may comprise a mixture of:

[0073] Sulfur compounds;

[0074] Boron-containing compounds; and

[0075] Surfactant.

[0076] That is, one or more sulfur-containing compounds may be mixed with one or more sulfur-containing compounds, one or more boron-containing compounds, and one or more surfactants to provide a mixture of three or more performance additives.

[0077] The three or more performance additives of the second component of the solvent system may comprise a mixture of:

[0078] Sulfur-containing compounds in an amount of ≥0.5% to <10% by weight of the solvent system,

[0079] a boron-containing compound in an amount of ≥0.5% to <10% by weight of the solvent system, and

[0080] Surfactant in an amount of ≥ 0.5% to < 10% by weight of the solvent system.

[0081] Optionally, the total amount of the three or more performance additives as the second component of the solvent system does not exceed about 10% by weight, based on the weight of the solvent system.

[0082] The three or more performance additives of the second component of the solvent system may comprise a mixture of:

[0083] Sulfur-containing compounds in an amount of ≥0.5% to <5% by weight of the solvent system,

[0084] a boron-containing compound in an amount of ≥0.5% to <5% by weight of the solvent system, and

[0085] Surfactant in an amount of ≥ 0.5% to < 5% by weight of the solvent system.

[0086] Optionally, the total amount of the three or more performance additives as the second component of the solvent system does not exceed about 5% by weight, based on the weight of the solvent system.

[0087] The three or more performance additives of the second component of the solvent system may comprise a mixture of:

[0088] a sulfur-containing compound in an amount of about 5% by weight of the solvent system,

[0089] a boron-containing compound in an amount of about 1% by weight of the solvent system, and

[0090] The surfactant is present in an amount of about 1% by weight of the solvent system.

[0091] The total amount of the three or more performance additives as the second component of the solvent system is about 7% by weight, based on the weight of the solvent system.

[0092] The three or more performance additives that are the second component of the solvent system may comprise (or consist essentially of) a mixture of:

[0093] a sulfur-containing compound in an amount of about 2% by weight of the solvent system,

[0094] a boron-containing compound in an amount of about 1% by weight of the solvent system, and

[0095] The surfactant is present in an amount of about 1% by weight of the solvent system.

[0096] The total amount of the three or more performance additives as the second component of the solvent system is about 4% by weight, based on the weight of the solvent system.

[0097] The one or more non-aqueous solvents as the first component of the solvent system are preferably selected from organic phosphate-based solvents, organic carbonate-based solvents and glyme-based solvents.

[0098] The one or more organophosphate-based solvents present as the first component of the solvent system of the present invention may be defined as described herein.

[0099] The one or more organophosphate-based solvents present as the first component of the solvent system may be cyclic compounds or acyclic compounds.

[0100] The one or more organophosphate based solvents as the first component of the solvent system are characterized by the fact that they contain phosphate groups, i.e. phosphorus atoms 1) doubly bonded to one oxygen atom and 2) singly bonded to three other oxygen atoms, which are further singly bonded to one or more carbon atoms.

[0101] Such compounds have the general formula R3(PO)4, where R can be identical or different in each case.

[0102] The preferred general formula of such compounds is RR'R''(PO4), wherein:

[0103] • R, R' and R'' can be independently selected from any linear or branched, substituted or unsubstituted C1 to C6 alkyl group; linear or branched, substituted or unsubstituted C1 to C6 alkenyl group; linear or branched, substituted or unsubstituted C1 to C6 alkoxy group; or substituted or unsubstituted group containing C3-C6 cycloalkyl, phenyl or heterocycle.

[0104] Very suitable electrolyte solvents as the first component of the solvent system include C1-C 10 Alkyl organophosphates, such as triethyl phosphate.

[0105] The preferred electrolyte composition of the present invention comprises a first component comprising one or more organic phosphate-based solvents, wherein the one or more organic phosphate-based solvents are present in an amount of about 50% or more, further preferably about 70% or more, further more preferably about 90% or more, and most preferably about 95% or more, based on the weight of the organic phosphate-based solvent (i.e., the first component of the solvent system). One such embodiment may comprise a first component comprising triethyl phosphate in an amount of about 90% or more based on the weight of the first component of the solvent system.

[0106] A highly preferred electrolyte composition of the present invention comprises a first component consisting essentially of one or more organic phosphate-based solvents, and desirably consisting of triethyl phosphate.

[0107] The one or more organic carbonate based solvents present as the first component of the solvent system of the present invention may be defined as described herein.

[0108] The one or more organic carbonate-based solvents present as the first solvent component may be cyclic or acyclic compounds characterized by the fact that they contain a carbonate group, i.e. a carbonyl group flanked by one or two alkoxy groups: R1O(C=O)OR2. The R1 and R2 groups are preferably independently selected (i.e. they may be identical or different from each other) from hydrogen; or C1 to C 20 - a cyclic or acyclic, branched or unbranched, substituted or unsubstituted alkyl group; or C1 to C 20 - a cyclic or acyclic, branched or unbranched, substituted or unsubstituted alkenyl group; or C1 to C 20 - a branched or unbranched, substituted or unsubstituted group containing a cycloalkyl group, a phenyl group or a heterocyclic ring.

[0109] Very suitable electrolyte solvents include C3-C 10 Cycloalkyl organic carbonates, such as propylene carbonate (C4H6O3) and ethylene carbonate (C3H4O3). Propylene carbonate (PC) (C4H6O3) exhibits particularly good compatibility with electrode materials, and the high solubility, wide liquidus range and high boiling point of the material also make this solvent advantageous for use in metal ion batteries, especially sodium ion batteries. Other very suitable organic carbonate-based compounds include diethyl carbonate (DEC), dimethyl carbonate (DMC), ethylene carbonate (EC), ethyl methyl carbonate (EMC), fluoroethylene carbonate (FEC) and vinylene carbonate (VC). Propylene carbonate (PC), diethyl carbonate (DEC) and ethylene carbonate (EC) are particularly preferred.

[0110] The preferred electrolyte composition of the present invention comprises a first component, wherein the first component comprises an organic carbonate-based solvent, wherein the organic carbonate-based solvent is present in an amount of at least 50%, further preferably at least 70%, further preferably at least 90%, and most preferably at least 95%, based on the weight of the organic carbonate-based solvent (i.e., the first component of the solvent system).

[0111] An electrolyte composition of the present invention may include a first component comprising a mixture of propylene carbonate in combination with one or more other organic carbonate-based compounds. Desirably, propylene carbonate is mixed with diethyl carbonate (DEC), preferably, wherein diethyl carbonate (DEC) is present in an amount of about 20% by weight of the first component of the solvent system.

[0112] An alternative highly preferred electrolyte composition of the present invention may comprise a first component comprising a mixture of ethylene carbonate (EC), diethyl carbonate (DEC) and propylene carbonate (PC), and an ideal weight ratio range is 1 to 4: 1 to 10: 1 to 10 weight / weight, a further ideal weight ratio is 1 to 2: 1 to 5: 1 to 2 weight / weight, and the most preferred weight ratio is 1: 2: 1 weight / weight.

[0113] The preferred electrolyte composition of the present invention can include a mixture of ethylene carbonate (EC) and dimethyl carbonate (DMC). These organic carbonate-based components are preferably present in a weight ratio of 1 to 20: 1 to 20 weight / weight, further preferably in a weight ratio of 1 to 10: 1 to 10 weight / weight, and also preferably in a weight ratio of 1 to 5: 1 to 5 weight / weight, and most preferably in a weight ratio of 1: 1 weight / weight.

[0114] Another electrolyte composition of the present invention may include a first component including a mixture of one or more organic phosphate-based solvents in combination with one or more organic carbonate-based compounds.

[0115] Desirably, triethyl phosphate is mixed with fluoroethylene carbonate (FEC), preferably wherein the fluoroethylene carbonate (FEC) is present in an amount of about 10 wt % based on the weight of the first component of the solvent system.

[0116] Alternatively, triethyl phosphate is mixed with vinylene carbonate (VC), preferably wherein the vinylene carbonate (VC) is present in an amount of about 3 wt % based on the weight of the first component of the solvent system.

[0117] The one or more glyme-based solvents present as the first component of the solvent system of the present invention may be defined as described herein.

[0118] The one or more glyme-based solvents present in the first component i) may be saturated acyclic polyethers, preferably containing no further functional groups. Glyme is also known as glycol diether.

[0119] Very suitable glyme-based solvents can be selected from ethylene glycol dimethyl ether (monoglyme), diethylene glycol dimethyl ether (diglyme), triethylene glycol dimethyl ether (triglyme) and tetraethylene glycol dimethyl ether (tetraglyme). Diethylene glycol dimethyl ether (diglyme) and tetraethylene glycol dimethyl ether (tetraglyme) are particularly preferred glyme-based solvents.

[0120] When a mixture of glyme-based compounds is used, it is convenient to express the amount of each of the one or more glyme-based solvents in terms of a weight ratio. For example, as discussed above, a highly preferred glyme-based solvent comprises a mixture of diglyme and tetraglyme as the first component of the solvent system, and this will ideally be in a weight ratio of 1 to 20: 1 to 20 weight / weight, further preferably 1 to 10: 1 to 10 weight / weight, also preferably 1 to 5: 1 to 5 weight / weight, and most preferably 1: 1 weight / weight.

[0121] The preferred electrolyte composition of the present invention comprises a first component comprising a mixture of diglyme and tetraglyme. Ideally, diglyme is present in an amount of about 50% by weight of the first component of the solvent system, and tetraglyme is present in an amount of about 50% by weight of the first component of the solvent system. Thus, the total amount of diglyme and tetraglyme is preferably about 100% by weight of the first component of the solvent system.

[0122] As discussed above, the second component of the solvent system according to the present invention may comprise one or more surfactants. The one or more surfactants of the present invention may be defined as described herein.

[0123] The total amount of the one or more surfactants used in the second component of the solvent system of the present invention may be >0.2% to ≤20% by weight of the solvent system, preferably ≥0.2% to ≤10% by weight of the solvent system, further preferably ≥0.2% to ≤4% by weight, very preferably ≥0.5% to ≤3% by weight, and ideally 0.5% to ≤2.5% by weight, based on the total weight of the electrolyte solvent system used in the electrolyte composition.

[0124] The amount of one or more surfactants used in the second component of the electrolyte composition according to the present invention may be >0% by weight of the solvent system, desirably >0.2% by weight of the solvent system, preferably >0.5% by weight, based on the total weight of the electrolyte solvent system used in the electrolyte composition.

[0125] The one or more surfactants used in the second component of the solvent system according to the present invention are performance additives and are preferably selected to enhance the ability of the electrolyte composition to wet the separator (particularly polyolefin separator) and / or electrode of the battery, which in turn advantageously promotes a longer battery cycle life. In addition, it is known in the literature that surfactants can cause non-dendritic metal plating / stripping (and also inhibit corrosion) due to their surface adsorption on different substrates. Preferred one or more surfactant additives are selected from anionic surfactants, cationic surfactants, nonionic (hydrophilic) surfactants and amphoteric (zwitterionic) surfactants, with anionic surfactants and nonionic (hydrophilic) surfactants being particularly preferred. Such surfactant additives are ideally selected from one or more of the following:

[0126] 1) Anionic (negatively charged) surfactants. Suitable examples include: carboxylates (such as alkyl carboxylates (e.g., fatty acid salts)), carboxylate fluorosurfactants; sulfates (such as alkyl sulfates (e.g., sodium lauryl sulfate), alkyl ether sulfates (e.g., sodium lauryl ether sulfate)); sulfonates (such as docusates (e.g., sodium dioctyl sulfosuccinate) and alkylbenzene sulfonates); and phosphates (such as alkyl aryl ether phosphates and alkyl ether phosphates (e.g., trioctyl phosphate);

[0127] 2) Zwitterionic (amphoteric) surfactants, which can be anionic, cationic, or nonionic, depending on the pH of the solution in which they are located. Examples include: RN + H2CH2COO - , RN + (CH3)2CH2CH2SO3 - , phospholipids (such as phosphatidylcholine (lecithin));

[0128] 3) Cationic surfactants with positive charge, such as RN + H3Cl - , RN + (CH3)3Cl - , diotadecyldimethylammonium chloride, cetylpyridinium chloride, benzalkonium chloride, cetyltrimethylammonium chloride (CTAC), and cetyltrimethylammonium bromide (CTAB); and

[0129] 4) Nonionic surfactants. These are uncharged and examples include: polyol esters (e.g. glycols, glycerides, sorbitan and sorbitan derivatives, such as fatty acid esters of sorbitan (Spans) and their ethoxylated derivatives (Tweens), polyoxyethylene esters and poloxamers containing block copolymers, for example Poloxamer 84, Poloxamer 105, Poloxamer 123, Poloxamer 124, Poloxamer 188, Poloxamer 237, Poloxamer 338, Poloxamer 407 and Poloxamer F127.

[0130] Most preferably, the one or more surfactants used in the second component of the solvent system according to the present invention comprise one or more surfactants containing nonionic block copolymers. Very suitable examples include poloxamers. Very specific examples include poloxamer 123.

[0131] As discussed above, the second component of the solvent system according to the present invention may comprise one or more sulfur-containing compounds. The one or more sulfur-containing compounds of the present invention may be defined as described herein.

[0132] The one or more sulfur-containing compounds used in the second component of the solvent system according to the present invention are performance additives and are preferably selected to achieve the formation of a stable cathode-electrolyte interface (CEI) at the cathode and / or a stable solid-electrolyte interface (SEI) at the anode, which in turn leads to advantages such as enhanced first cycle coulombic efficiency (FCE = first cycle coulombic efficiency) and enhanced cycle life; alternatively, the additive may significantly decompose preferentially in the first cycle, which may result in low first cycle efficiency, but then improve subsequent cycle stability.

[0133] Suitable sulfur-containing compounds may include cyclic and / or acyclic sulfur-containing compounds.

[0134] Preferably, the sulfur-containing compound is a sulfone-containing compound, a sulfate-containing compound or a sulfonate-containing compound.

[0135] In other words, the sulfur-containing compound can have a sulfonyl functional group attached to two carbon atoms (sulfone), two oxygen atoms (sulfate), or one carbon atom and one oxygen atom (sulfonate) in a cyclic or non-cyclic structure. When the sulfonate is cyclic, the compound can be referred to as a sultone.

[0136] As used herein, the term "sulfone" means a central hexavalent sulfur atom double-bonded to each of two oxygen atoms and having a single bond to each of two carbon atoms.

[0137] As used herein, the term "sulfate" means a central hexavalent sulfur atom double-bonded to two of the oxygen atoms and having single bonds to two additional oxygen atoms, each of which is further single-bonded to a carbon atom.

[0138] As used herein, the term "sulfonate" means a central hexavalent sulfur atom double-bonded to two oxygen atoms; which has a single bond to one carbon atom; and a single bond to another oxygen atom, which is further single-bonded to a carbon atom, which, if cyclically linked to another carbon atom bonded to the sulfur atom, would be a sultone.

[0139] Such compounds have the general formula RY(S=O)2Y'R', wherein:

[0140] • Y and Y' are independently selected from C or O (i.e. they may be the same or different from each other);

[0141] • when Y and Y' are the same, R and R' may be independently selected from (i.e. they may be the same as or different from each other) any linear or branched, substituted or unsubstituted C1 to C6-alkyl group; a linear or branched, substituted or unsubstituted C1 to C6-alkenyl group; a linear or branched, substituted or unsubstituted C1 to C6-alkoxy group; or wherein R and R' may independently or together form a substituted or unsubstituted C3-C6-cycloalkyl, phenyl or heterocyclic containing group; and

[0142] • When Y and Y' are different from each other, R' can be independently selected from any linear or branched, substituted or unsubstituted C1 to C6-alkyl group; linear or branched, substituted or unsubstituted C1 to C6-alkenyl group; linear or branched, substituted or unsubstituted C1 to C6-alkoxy group; or wherein R and R' can independently or together form a substituted or unsubstituted group containing C3-C6-cycloalkyl, cycloalkenyl, phenyl or heterocycle.

[0143] In some embodiments, the general formula of such compounds is R-SO2-R', wherein R and R' can be independently selected from (i.e., they can be the same as or different from each other) any linear or branched, substituted or unsubstituted C1 to C6-alkyl group; a linear or branched, substituted or unsubstituted C1 to C6-alkenyl group; a linear or branched, substituted or unsubstituted C1 to C6-alkoxy group; or wherein R and R' can independently or together form a substituted or unsubstituted group containing C3-C6-cycloalkyl, phenyl or heterocycle.

[0144] Preferably, such compounds have the general formula RO(S=O)2OR', wherein R and R' can be independently selected from (i.e. they can be the same or different from each other) any linear or branched, substituted or unsubstituted C1 to C6-alkyl group; a linear or branched, substituted or unsubstituted C1 to C6-alkenyl group; a linear or branched, substituted or unsubstituted C1 to C6-alkoxy group; or wherein R and R' can independently or together form a substituted or unsubstituted group containing C3-C6-cycloalkyl, phenyl or heterocycle.

[0145] Very preferably, the sulfur-containing compound is selected from cyclic sulfates (such as 1,3-propanediol cyclic sulfate (PCS), also known as 1,3,2-dioxathiolane 2,2-dioxide (DTD or (CH2)3SO4)); 1,5,2,4-dioxadithiolane 2,2,4,4-tetraoxide; or 1,3,2-dioxathiolane 2,2-dioxide.

[0146] Suitable examples of cyclic sulfones include sulfolane ((CH2)4SO2), 3-methylsulfolane ((CH3)CH(CH2)3SO2) and trimethylsulfone ((CH2)3SO2). Suitable examples of non-cyclic sulfones include methylphenylsulfone ((CH3)(C6H5)SO2).

[0147] Suitable examples among the examples of sultone include: 1-propylene 1,3-sultone ((CH) 2 CH 2 SO 3 ) and 1,3-propane sultone (CH 2 ) 3 SO 3 .

[0148] Most preferably, the sulfur-containing compound is 1,3-propylene glycol cyclic sulfate (PCS).

[0149] Based on the total weight of the electrolyte solvent system used in the electrolyte composition, the total amount of one or more sulfur-containing compounds used in the second component of the solvent system according to the present invention is >0.5% to ≤10% by weight of the solvent system, preferably ≥0.6% to ≤6% by weight of the solvent system, further preferably ≥0.6% to ≤4% by weight, very preferably ≥0.6% to ≤3% by weight, ideally 0.6% to ≤2.5% by weight.

[0150] The amount of one or more sulfur-containing compounds used in the second component of the solvent system according to the present invention may be >0% by weight of the solvent system, desirably >0.2% by weight of the solvent system, preferably >0.5% by weight, based on the total weight of the electrolyte solvent system used in the electrolyte composition.

[0151] In one embodiment, the sulfur-containing compound as a performance additive according to the present invention does not include dimethyl sulfoxide (DMSO).

[0152] As discussed above, the second component of the solvent system according to the present invention may comprise one or more boron-containing compounds. The one or more boron-containing compounds of the present invention may be defined as described herein.

[0153] The boron-containing compound used in the second solvent component of the solvent system according to the present invention is a performance additive and is preferably selected to achieve the formation of a stable cathode-electrolyte interface (CEI) at the cathode and / or a stable solid-electrolyte interface (SEI) at the anode, which in turn leads to advantages such as enhanced first cycle coulombic efficiency and / or enhanced cycle life.

[0154] Suitable boron-containing compounds may include cyclic and / or acyclic boron-containing compounds.

[0155] Preferably, the one or more boron-containing compounds are borate esters or boroxines.

[0156] In other words, the one or more boron-containing compounds may have a central boron atom attached to three oxygen atoms, each of which is further single-bonded to a carbon or silicon atom (boric acid ester). Or the one or more boron-containing compounds may comprise a 6-membered heterocyclic ring structure consisting of three alternating boron atoms and oxygen atoms linked together by shared single bonds. Each boron atom is further single-bonded to a carbon atom or oxygen outside the heterocyclic ring structure.

[0157] As used herein, the term "borate ester" refers to a central trivalent boron atom singly bonded to three oxygen atoms, each of which is further singly bonded to a carbon or silicon atom.

[0158] As used herein, the term "boroxine" refers to a 6-membered heterocyclic compound composed of alternating single-bonded trivalent boron atoms and divalent oxygen atoms, each boron atom further single-bonded to an oxygen or carbon atom outside the heterocyclic structure.

[0159] The general formula of such borate compounds is B(OYR)3, where Y and R can be the same or different in each case of attachment. More specifically, this can be written as:

[0160] B(OYR)(OY'R')(OY''R''), where

[0161] • Y, Y' and Y" are independently selected from C or Si (ie they may be the same or different from each other); and

[0162] • R, R' and R" can be independently selected from hydrogen; any linear or branched, substituted or unsubstituted C1 to C6-alkyl group; a linear or branched, substituted or unsubstituted C1 to C6-alkenyl group; a linear or branched, substituted or unsubstituted C1 to C6-alkoxy group; or a substituted or unsubstituted group containing C3-C6-cycloalkyl, phenyl or heterocycle.

[0163] Further preferably, the boron-containing compound is selected from acyclic boric acid esters.

[0164] Suitable examples include tris(trimethylsilyl)borate (TMSB);

[0165] Tris(2,2,2-trifluoroethyl)borate;

[0166] trimethyl borate; and

[0167] Triethyl borate.

[0168] The general formula of such boroxine compounds is B3(YR)3O3, where Y and R can be the same or different in each case of attachment. More specifically, this can be written as:

[0169] B a (YR) b (O) c ,in

[0170] • Y is independently selected from C or O (ie they may be the same or different from each other); and

[0171] • R may be identical or different in each case and may be independently selected from hydrogen; any linear or branched, substituted or unsubstituted C1 to C6-alkyl group; a linear or branched, substituted or unsubstituted C1 to C6-alkenyl group; a linear or branched, substituted or unsubstituted C1 to C6-alkoxy group; or a substituted or unsubstituted C3-C6-cycloalkyl, phenyl or heterocyclic containing group; and

[0172] • a = b = c, where a, b, and c are each 3.

[0173] Suitable examples include:

[0174] trimethoxyboroxine; and

[0175] Trimethylboroxine.

[0176] Most preferably, the boron-containing compound is tris(trimethylsilyl)borate (TMSB).

[0177] The total amount of the one or more boron-containing compounds used in the second component of the solvent system according to the present invention is >0.5% to ≤10% by weight of the solvent system, preferably ≥0.6% to ≤6% by weight of the solvent system, further preferably ≥0.6% to ≤4% by weight, very preferably ≥0.6% to ≤3% by weight, and ideally 0.6% to ≤2.5% by weight, based on the total weight of the electrolyte solvent system used in the electrolyte composition.

[0178] The amount of the one or more boron-containing compounds used in the second component of the solvent system according to the present invention may be >0% by weight of the solvent system, desirably >0.2% by weight of the solvent system, preferably >0.5% by weight, based on the total weight of the electrolyte solvent system used in the electrolyte composition.

[0179] The electrolyte composition according to the invention may further comprise one or more additional compounds which may or may not be solvents.

[0180] Examples of such additional compounds include flame retardant compounds (such as compounds containing polyalkyl phosphates, preferably compounds containing non-fluorinated polyalkyl phosphates), diluents (such as compounds containing hydrofluoroethers, preferably compounds containing hydrofluoroalkyl ethers), glycol ether acetates, ionic liquids, and any solvents that can promote the reduction of electrolyte viscosity by acting as an inert diluent (such as hydrofluoroalkyl ethers, preferably 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (HFE or TTE)).

[0181] The electrolyte composition according to the present invention may also optionally contain one or more other performance additives, the amount of which is generally <15% by weight, preferably <10% by weight, and further preferably 0.1 wt % to <5% by weight of the total weight of the solvent system used in the electrolyte composition. Such performance additives preferably act at the electrolyte-electrode interface rather than in the bulk of the electrolyte, such as tris(trimethylsilyl)phosphite or tris(trimethylsilyl)phosphate.

[0182] Suitable other performance additives may be selected from: polymerizable additives for promoting overcharge protection, such as biphenyl, diphenylamine, dimethoxydiphenylsilane (DDS), 3-chloroanisole (3CA), N-phenylmaleimide, xylene (methyl substituted benzene) and cyclohexylbenzene; additives for promoting overcharge protection based on redox shuttle mechanism, such as 2,5-di-tert-butyl-1,4-dimethoxybenzene (DDB), 4-tert-butyl-1,2-dimethoxybenzene (TDB), 1,4-bis(trimethylsilyl)-2,5-dimethoxybenzene (BTMSDB) and 1,4-bis(2-methoxyethyl)-1,4-dimethoxy ... additives for imparting further flame retardant properties to the electrolyte, such as dimethyl methylphosphonate (DMMP), ethoxy-pentafluoro-cyclotriphosphazene (N3P3F5OCH2CH3, EFPN), tris(2,2,2-trifluoroethyl)phosphite and / or tris(2,2,2-trifluoroethyl)phosphate (TFEP), methyl nonafluorobutyl ether (MFE) and silane-Al2O3 nanoparticles; additives for promoting better high temperature cycling, such as succinic anhydride; and additives for in situ rendering inert to unwanted decomposition products (such as HF, water or CO2), such as zeolites.

[0183] The electrolyte composition according to the present invention may further comprise one or more non-metallic supporting electrolyte salts, which are referred to herein as "supporting salts". For the purposes of this disclosure, "supporting salts" refers to any salt that is not a metal-containing salt but promotes the absorption of metal cations (i.e., Na + ) is transferred from the cathode to the anode and vice versa. However, the non-metallic supporting salt does not participate in the electrochemical process of the electrochemical cell.

[0184] Very preferably, the non-metallic supporting salt may be selected from one or more quaternary ammonium salts in which one nitrogen atom is singly bonded to four alkyl groups to form a soluble cationic compound. Suitable non-metallic supporting salts include tetrabutylammonium hexafluorophosphate (TBAPF6) and tetraethylammonium hexafluorophosphate (TEAPF6).

[0185] Preferably, the non-metallic supporting salt is tetrabutylammonium hexafluorophosphate (TBAPF6).

[0186] It is convenient to express the concentration of one or more non-metallic supporting salts in the solvent system as their mass molar concentration (m); that is, the total number of moles of one or more non-metallic supporting salts (i.e., solute) per kilogram or 1000 g of the solvent system (i.e., the combined weight of the first component and the second component). Preferably, the mass molar concentration of each non-metallic supporting salt in a) is in the range of 0.1 mol / kg to 5 mol / kg, further preferably in the range of 0.1 mol / kg to ≤2.5 mol / kg. Very preferably, especially when the non-metallic supporting salt is TBAPF6, the mass molar concentration is in the range of 0.1 mol / kg to ≤2.5 mol / kg, most preferably about 1.0 mol / kg.

[0187] The electrolyte composition of the present invention is particularly useful in electrochemical cells, preferably sodium-based electrochemical cells. Therefore, in another aspect, the present invention provides an electrochemical cell comprising the electrolyte composition defined herein. Preferred electrochemical cells include metal ion batteries (e.g. sodium ion batteries), anode-free batteries (e.g. sodium anode-free batteries) and alkali metal batteries (e.g. sodium metal batteries).

[0188] The electrolyte composition of the present invention is particularly useful in metal ion batteries. Therefore, in another aspect, the present invention provides a metal ion battery comprising a negative electrode, a positive electrode and an electrolyte composition as defined herein. The metal ion battery of the present invention may be selected from an alkali metal battery and a non-alkali metal battery.

[0189] When an alkali metal battery is used, it is preferred that the alkali metal battery is selected from one or more of a sodium ion battery, a lithium ion battery and a potassium ion battery; preferably, the alkali metal battery is selected from one or more of a sodium ion battery, a lithium ion battery and a potassium ion battery; most preferably, the alkali metal battery is a sodium ion battery. When a non-alkali metal ion battery is used, it is preferred that the non-alkali metal ion battery is a zinc ion battery, an aluminum ion battery, a calcium ion battery or a magnesium ion battery.

[0190] The metal ion battery of the present invention may use a negative electrode (anode) containing a negative electrode active material commonly used in the art. For example, the negative electrode (anode) containing a negative electrode active material may be one or more of a graphite material, soft carbon, hard carbon, carbon fiber, mesophase carbon microspheres, silicon-based materials, tin-based materials, P-based materials, Sb-based materials, SnSb-based materials, other types of materials that store charge via conversion and / or alloying type reactions (such as simple / binary / ternary oxides of Fe, Cu, Ni, Mn, etc.) and materials that store charge via classical intercalation type reactions such as lithium titanium oxide, different types of sodium titanates, titanium dioxide, etc.); and any combination of one or more of these materials, such as Carbon / Sb, carbon / P, carbon / Fe2O3, or as a mixture produced by physical blending (such as carbon and Sb blended together by physical or chemical mixing methods such as ball milling or spray drying), or a mixture produced via an in situ reaction (via an appropriate synthesis route such as solvent / hydrothermal, sol-gel, solution-based, reflux, co-precipitation or solid-state reaction with or without a subsequent heating / pyrolysis step), the latter of which may also produce doped materials (such as carbon doped with Sb or P or Sn) and / or substituted materials (such as replacing Fe2O3 with a small amount of TiO2).

[0191] The metal ion battery disclosed herein may include a separator located between the cathode and anode current collectors. Preferably, the polyolefin separator has a thickness of 25 μm or less. Preferably, the thickness is 16 μm or less.

[0192] The metal ion battery of the present invention can be used in energy storage devices such as batteries, rechargeable batteries, electrochemical devices and electrochromic devices.

[0193] Specifically, when the metal ion battery is a sodium ion or potassium ion battery, the sodium ion or potassium ion battery may use a negative electrode (anode) comprising a negative electrode active material having a structure suitable for inserting / removing sodium or potassium ions during charge / discharge. Preferably, a carbonaceous material may be used as the negative electrode active material. Very preferably, the negative electrode active material may be a non-graphitizable carbonaceous material, most preferably a hard carbonaceous material. Suitable hard carbon negative electrode active materials include Kuranode Type 1 provided by Kureha.

[0194] Specifically, when the metal ion battery is a sodium ion battery, the sodium ion battery may include a positive electrode (cathode) comprising any sodium-containing positive electrode active material suitable for inserting / removing sodium ions during charge / discharge. Examples of these materials include sodium transition metal oxides, polyanionic compounds (including fluorinated polyanionic compounds), Prussian blue analog (PBA) compounds (such as Prussian white or Berlin green), materials that store sodium via conversion reactions, sodium transition metal fluorides, fluoride oxides, phosphates, sulfates and silicates (and their fluorinated forms). A preferred example is sodium transition metal oxide.

[0195] Preferred sodium transition metal oxides have the following general formula:

[0196] A 1±δ M 1 V M 2 W M 3 X M 4 Y M 5 Z O 2-c

[0197] in

[0198] A is one or more alkali metals selected from sodium, potassium and lithium;

[0199] M 1 comprising one or more redox-active metals in oxidation state +2, preferably selected from nickel, copper, cobalt and manganese;

[0200] M 2 Contains metals having an oxidation state greater than 0 to less than or equal to +4;

[0201] M 3 Contains metals in oxidation state +2;

[0202] M 4 Contains metals having an oxidation state greater than 0 to less than or equal to +4;

[0203] M 5 Contains metals in oxidation state +3;

[0204] in

[0205] 0≤δ≤1;

[0206] V>0;

[0207] W ≥ 0;

[0208] X ≥ 0;

[0209] Y ≥ 0;

[0210] At least one of W and Y > 0

[0211] Z ≥ 0;

[0212] C is in the range of 0≤c<2

[0213] Among them, V, W, X, Y, Z and C are selected to maintain electrochemical neutrality.

[0214] Ideally, metal M 2 Contains one or more transition metals, preferably selected from manganese, titanium and zirconium; M 3 Preferably, it is one or more selected from magnesium, calcium, copper, tin, zinc and cobalt; M 4 Contains one or more transition metals, preferably selected from manganese, titanium and zirconium; M 5 Preferably, it is one or more selected from aluminum, iron, cobalt, tin, molybdenum, chromium, vanadium, scandium and yttrium.

[0215] Particularly preferred positive active materials for sodium ion batteries will be nickelate-based materials. Sodium-containing active materials having any crystal structure may be used, however, it is preferred to use structures that are O3 or P2 or derivatives thereof, but in particular it is also possible that the cathode active material will contain a mixture of phases, i.e. it will have a non-uniform structure consisting of several different crystal forms. For example, the cathode active material will contain a compound having the above general formula in the form of a mixture of O3 and P2 phases. The ratio of O3:P2 phases is preferably 1 to 99: 99 to 1.

[0216] Specifically, when the metal ion battery is a potassium ion battery, the potassium ion battery may include a positive electrode (cathode) comprising any potassium-containing positive electrode active material that is suitable for inserting / removing potassium ions during charge / discharge. Examples of these active materials include oxide-based materials, phosphate- and / or fluorophosphate-based materials, or PBA compounds. A particularly preferred potassium-containing positive electrode active material is a P3-type K 0.5 [Mn 0.8 Fe 0.1 Ni 0.1 ]O2 layered oxide, K2MnFe(CN)6 or KVPO4F.

[0217] Specifically, when the metal ion battery is a lithium ion battery, the lithium ion battery may use a negative electrode comprising a negative electrode active material having a structure suitable for achieving insertion / removal of lithium ions during charge / discharge. Preferably, a carbonaceous material is used as the active negative electrode material. Very preferably, the carbonaceous material is a graphitizable carbonaceous material, most preferably a graphite-containing material. Suitable graphite negative electrode active materials include graphite provided by MTI.

[0218] Specifically, when the metal ion battery is a lithium ion battery, the lithium ion battery may include a positive electrode (cathode) comprising any lithium-containing positive electrode active material suitable for inserting / removing lithium ions during charge / discharge. Examples of these materials include lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide (NCA), transition metal phosphates and lithium iron phosphate. A particularly preferred lithium-containing positive electrode active material is LiNi 0.5 Co 0.2 Mn 0.3 O2 (NCM523), LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811) or NCA.

[0219] The present invention also provides the use of an electrolyte composition as defined herein in a metal ion battery. Such a metal ion battery may be as defined above.

[0220] The electrolyte composition of the present invention is also particularly useful in anode-free sodium batteries, also known as in-situ sodium plating batteries. Such anode-free sodium batteries can be used in energy storage devices such as batteries, rechargeable batteries, electrochemical devices and electrochromic devices.

[0221] Therefore, in another aspect, the present invention provides an anode-free sodium battery comprising an electrolyte composition as defined herein. More specifically, in one aspect, the present invention provides:

[0222] An anode-free sodium battery comprising:

[0223] a cathode comprising one or more sodium-containing active materials;

[0224] Anode current collector;

[0225] a separator positioned between the cathode and anode current collectors; and

[0226] An electrolyte composition as defined herein.

[0227] In another aspect, the present invention also provides the use of the electrolyte composition defined herein in an anode-free sodium battery.

[0228] As used herein, "anode-free sodium battery" refers to a battery in which the operating principle of the battery involves the extraction / intercalation of sodium metal cations (Na + ) and deposition and plating / removal and stripping of sodium metal (Na) at the anode current collector. During the first charge cycle of an anode-free sodium battery, a sodium metal anode is formed in situ on the anode current collector as sodium metal cations are reduced and deposited as sodium metal on the anode current collector.

[0229] When the anode-free sodium battery is fully discharged, the anode current collector contains only trace amounts of sodium metal or significantly less sodium metal than in the case of a fully charged battery, most of which has been oxidized to form sodium metal cations present in the electrolyte and / or stored in the cathode. When the anode-free sodium battery is fully charged, the anode current collector includes a sodium layer in electrical contact with the anode current collector, and the amount of sodium in the cathode is correspondingly less. The sodium layer in electrical contact with the anode current collector may span the entire surface of the anode current collector, or it may be deposited in some areas of the anode current collector. However, where sodium is deposited, it is preferred that any such sodium layer is uniform and homogeneous.

[0230] The anode-free batteries disclosed herein may include a separator positioned between the cathode and anode current collectors. Polyolefin separators are preferred.

[0231] The cathode generally comprises a sodium-containing active material disposed on one or more surfaces of a (cathode) current collector. The cathode current collector and the anode current collector may each independently be made of any suitable conductive material. For example, the cathode current collector, the anode current collector, or both the cathode current collector and the anode current collector may be formed of a metal; such as nickel, aluminum, titanium, copper, gold, silver, platinum, aluminum alloys, stainless steel, or any other metal substrate (similar to the current collectors commonly used in current sodium-ion batteries).

[0232] The cathode current collector, the anode current collector, or both the cathode current collector and the anode current collector may be formed of aluminum or an aluminum alloy (e.g., an alloy of aluminum and one or more of Mg, Mn, Cr, Zn, Si, Fe, and Ni). Very preferably, both the cathode current collector and the anode current collector include an aluminum current collector. Alternatively, copper, magnesium, carbon paper / foil / substrate, and tin may also be used as current collector materials.

[0233] The cathode current collector and the anode current collector can be formed into any suitable shape that is compatible with the overall design of the electrochemical cell. For example, the cathode current collector and the anode current collector can each be independently formed into a foil, a flat plate, a mesh, a net, a lath, a perforated metal or an embossing, or a combination of these shapes (e.g., a mesh flat plate). If desired, irregularities can be formed on one or more surfaces of the cathode current collector and / or the anode current collector, for example by etching one or more surfaces of the current collector. Very preferably, the anode current collector is formed of aluminum or an aluminum alloy and includes a foil or mesh shape.

[0234] Preferably, the anode current collector further comprises one or more nucleation layers formed on one or more surfaces of the anode current collector prior to the initial first charging cycle of the anode-free sodium battery. Very preferably, such one or more nucleation layers comprise one or more carbon-containing nucleation layers. Since the anode current collector is formed with one or more nucleation layers on one or more surfaces of the anode current collector, during the first charging cycle of the anode-free sodium battery, the metal cations are reduced and deposited as sodium metal on the one or more nucleation layers. The surface of the current collector or nucleation layer may also be pre-coated or post-coated with sodium or other materials, and physical vapor deposition is a useful means of achieving such a coating.

[0235] As used herein, the term "nucleation layer" refers to any coating or layer disposed on one or more surfaces of a "virgin" anode current collector prior to the initial first charge cycle of an anode-free sodium battery. The use of a nucleation layer achieves a more uniform and homogeneous sodium metal deposition compared to a current collector without such a nucleation layer. A particularly preferred nucleation layer is any coating or layer that will result in a reduction in the "nucleation overpotential" for sodium metal electroplating.

[0236] When sodium metal is deposited on the anode current collector via constant current (galvanostatic) cycling, for the same constant current value, during steady-state conditions, the potential rises to a higher value (but still below 0 V, vs. Na / Na + ), the potential for sodium plating will first decrease (to a more negative value below 0 V, relative to Na / Na + ).

[0237] Thus, the "nucleation overpotential" for sodium deposition is defined herein as the difference between the most negative potential and the steady-state plating potential. Thus, one skilled in the art can readily measure the nucleation overpotential for sodium deposition using an anode current collector comprising one or more nucleation layers formed on the surface of the anode current collector and compare it to the nucleation overpotential for sodium deposition using a "pristine" anode current collector to determine the preferred nucleation layer described herein. This can be done in a half-cell or three-electrode cell constructed using common knowledge.

[0238] As discussed above, advantageously, the one or more nucleation layers enable deposition of sodium metal atoms and atomic clusters at and across the surface of the anode current collector, thereby facilitating more uniform electroplating while also minimizing parasitic reactions.

[0239] One or more nucleation layers may be formed across most (or the entire 100%) of one or more surfaces of the anode current collector, or may be formed as a partial coating by design (e.g., one or more nucleation layers are formed on some regions of such a surface—these regions will be homogenous and uniform within the region). One or more nucleation layers preferably include one or more negative electrode active material layers (e.g., thin layers such as 0.1 μm to 1000 μm), which may or may not be mixed with any type of conductive additive, such as carbon black (to enhance the electronic conductivity of the negative electrode active material) and / or a binder material that is compatible with water or an organic solvent.

[0240] Most preferably, the one or more nucleation layers comprise one or more carbon-containing nucleation layers, and most preferably, the one or more carbon-containing nucleation layers have a thickness of about 10 Angstroms to about 1000 μm.

[0241] Suitable one or more carbon-containing nucleation layers may include: carbon black, carbon nanotubes, carbon nanofibers, graphite / graphene, hard carbon, glassy carbon, soft carbon, activated carbon (e.g., in fiber form), or combinations thereof. In some cases, the carbon-containing nucleation layer may include amorphous carbon (e.g., carbon black, such as TIMCAL Super C65). Techniques such as blade coating, slot coating, ultrasonic spray deposition, screen printing, physical vapor deposition (PVD), and chemical vapor deposition (CVD) may also be used to prepare such a carbon-containing nucleation layer.

[0242] Alternatively, before the initial first charging cycle of the anode-free sodium battery, the anode current collector also includes two or more nucleation layers formed on one or more surfaces of the anode current collector. In one embodiment, such two or more nucleation layers are preferably two or more carbon-containing nucleation layers.

[0243] Alternatively, the anode current collector disclosed herein does not include one or more nucleation layers on one or more surfaces of the anode current collector prior to the initial first charge cycle of the anode-free sodium battery. Thus, the anode current collector is "pristine" prior to the initial first charge cycle of the anode-free sodium battery. As used herein, the phrase "pristine" means that it is in its "as manufactured" state prior to the initial first charge cycle of the anode-free sodium battery. In other words, the anode current collector is substantially the pure material from which it is formed, free of impurities (e.g., surface oxide layers, etc.). Thus, the anode current collector is not coated with one or more nucleation layers (as discussed above), conventional active materials, binders, etc.

[0244] After charge and discharge cycles, the anode current collector in a completely sodium-stripped state may be the same as the "pristine" state, or it may incorporate one or more layers substantially comprising sodium-containing materials. It may also contain inorganic-rich and / or organic-rich materials from, for example, the electrolyte composition and its decomposition products.

[0245] Based on the disclosure herein, it is believed that any type of sodium-containing active material can be used as a cathode in a sodium-ion battery to form an anode-free sodium battery according to the present invention. Therefore, the sodium-containing active material used in the anode-free sodium battery can be defined according to the sodium-containing active material used in the sodium-ion battery as described above.

[0246] The electrolyte compositions of the present invention are also particularly useful in sodium metal batteries. Such sodium metal batteries can be used in energy storage devices such as batteries, rechargeable batteries, electrochemical devices, and electrochromic devices.

[0247] Therefore, in another aspect, the present invention provides a sodium metal battery comprising an electrolyte composition as defined herein. More specifically, in one aspect, the present invention provides:

[0248] A sodium metal battery comprising:

[0249] a cathode comprising one or more cathode active materials;

[0250] an anode current collector comprising sodium metal as an anode active material;

[0251] a separator positioned between the cathode and anode current collectors; and

[0252] An electrolyte composition as defined herein.

[0253] In another aspect, the present invention also provides use of the electrolyte composition defined herein in a sodium metal battery.

[0254] Ideally, the anode current collector includes a sodium metal layer or sodium metal film, which is generally greater than 0 to about 1000 μm thick. Such a layer or film is generally coated / deposited on the surface of the anode current collector using a deposition technique (e.g., physical vapor deposition) or a coating technique, such as mixing sodium metal with a binder material (such as PVDF) and optionally containing a conductive additive (such as carbon black and / or carbon nanotubes), while mixing using a non-aqueous solvent such as N-methylpyrrolidone (NMP), and then coating via a technique such as a doctor blade method or a slot method.

[0255] Preferably, the anode current collector is any substrate commonly used in anode-free batteries as defined above. Examples include: aluminum foil, copper foil and carbon paper.

[0256] Suitable cathode active materials may be sodium-containing active materials, which are defined as sodium-containing active materials for use in sodium-ion batteries as described above. Alternatively, suitable cathode active materials may include sodium-deficient cathode materials such as FeS2, TiS2, Na 0+x FePO4、Na 0+x VPO4F、Na 0+x Fe2(CN)6、Na 0+x MnFe(CN)6 (wherein x can be 0 to 1), etc.

[0257] In another aspect, the present invention also provides a method of operating one or more metal ion batteries disclosed herein and / or one or more anode-free sodium batteries disclosed herein. The method comprises the step of cycling one or more batteries at a C rate of about C / ≥2, more preferably at a C rate of about C / ≥5.

[0258] In one embodiment, the method includes the step of discharging one or more batteries at a discharge C-rate of about C / ≥2, more preferably at a rate of about C / ≥5. For the avoidance of any doubt, the discharge C-rate is the discharge current divided by the theoretical current consumption at which the battery outputs its nominal rated capacity over a specified hour period. Therefore, a discharge C-rate of C / ≥2 means that the discharge current will discharge the entire battery in 2 hours or more. Similarly, a discharge C-rate of C / ≥5 means that the discharge current will discharge the entire battery in 5 hours or more. In some cases, the step of discharging one or more batteries at a discharge C-rate of about C / ≥7, optionally at a C-rate of about C / ≥10, optionally at a C-rate of about C / ≥20, optionally at a C-rate of about C / ≥50.

[0259] In one embodiment, the step of discharging the one or more batteries at a discharge C-rate of C / ≥2 to C / ≤200, further preferably C / ≥2 to C / ≤100, further preferably C / ≥2 to C / ≤50, further preferably C / ≥2 to C / ≤20, and ideally at a discharge C-rate of C / ≥2 to C / ≤10.

[0260] Therefore, the purpose of the method of operating one or more batteries according to the present invention is to utilize the electrolyte composition according to the present invention in the battery at a low C rate such as C / 5, C / 10 or even C / 20 to obtain excellent long-term cycling stability and high battery performance. Therefore, the electrolyte composition according to the present invention is particularly useful for stationary applications that require capacity release over a longer time span.

[0261] Another aspect of the present invention is to provide a device, which includes one or more metal ion batteries disclosed herein, and / or one or more anode-free sodium batteries disclosed herein, and / or one or more sodium metal batteries disclosed herein. Typical devices may include equipment that can be used for fixed or mobile applications, such as battery packs.

[0262] In one embodiment, the device also includes one or more metal ion batteries having an electrolyte composition comprising one or more metal-containing salts in a concentration exceeding that of the present invention. Ideally, this will be greater than 0.2 mol / kg. Thus, one or more metal ion batteries comprising an electrolyte composition according to the present invention may be mixed with one or more metal ion batteries comprising an electrolyte composition not according to the present invention.

[0263] In another aspect, the present invention also provides a method for obtaining usable energy from an electrochemical cell, comprising:

[0264] An electrochemical cell is operated using an electrolyte composition comprising a solvent system comprising:

[0265] A first component comprising one or more non-aqueous solvents;

[0266] a second component comprising one or more performance additives selected from the group consisting of sulfur-containing compounds, boron-containing compounds, and surfactants; and

[0267] Wherein, the electrolyte composition further comprises one or more metal-containing salts at a concentration of 0 mol / kg to ≤0.2 mol / kg.

[0268] The electrolyte composition and / or the electrochemical cell may be further defined as described above or according to the embodiments disclosed herein.

[0269] In one embodiment, the method further comprises providing an electrochemical cell and then operating the electrochemical cell with an electrolyte composition according to the present invention. The step of operating the electrochemical cell preferably comprises cycling the electrochemical cell at a C rate of about C / ≥2, more preferably at a C rate of about C / ≥5. In one embodiment, the method comprises the step of discharging the electrochemical cell at a discharge C rate of about C / ≥2, more preferably at a rate of about C / ≥5.

[0270] As described above, a discharge C rate of C / ≥2 means that the discharge current will discharge the entire battery in 2 hours or more. Similarly, a discharge C rate of C / ≥5 means that the discharge current will discharge the entire battery in 5 hours or more. In some cases, the step of discharging one or more batteries at a discharge C rate of about C / ≥7, optionally at a C rate of about C / ≥10, optionally at a C rate of about C / ≥20, optionally at a C rate of about C / ≥50.

[0271] In one embodiment, the step of discharging the one or more batteries at a discharge C-rate of C / ≥2 to C / ≤200, further preferably C / ≥2 to C / ≤100, further preferably C / ≥2 to C / ≤50, further preferably C / ≥2 to C / ≤20, and ideally at a discharge C-rate of C / ≥2 to C / ≤10.

[0272] In one embodiment, the method further comprises associating or integrating the usable energy from the electrochemical cell with one or more additional electrochemical cells having one or more metal-containing salts at a concentration greater than 0.2 mol / kg.

[0273] In another aspect, the present invention also provides a method for manufacturing an electrochemical cell as defined herein. Preferably, the method comprises:

[0274] An electrolyte composition comprising a solvent system is introduced into an electrochemical cell, the solvent system comprising:

[0275] A first component comprising one or more non-aqueous solvents;

[0276] a second component comprising one or more performance additives selected from the group consisting of sulfur-containing compounds, boron-containing compounds, and surfactants; and

[0277] Wherein, the electrolyte composition further comprises one or more metal-containing salts in a concentration of 0 mol / kg to ≤0.2 mol / kg.

[0278] The electrolyte composition and / or the electrochemical cell may be further defined as described above or according to the embodiments disclosed herein.

[0279] In one embodiment, the manufacturing method further comprises providing an electrochemical cell and then introducing the electrolyte composition according to the present invention into the electrochemical cell.

[0280] In one embodiment, the electrochemical cell is prepared by the manufacturing method defined herein.

[0281] On the other hand, the present invention also provides a device comprising an electrochemical cell disclosed herein. The device may further include one or more electrochemical cells having an electrolyte composition comprising one or more metal-containing salts in a concentration exceeding that of the present invention. Ideally, the concentration will be greater than 0.2 mol / kg. Therefore, an electrochemical cell comprising an electrolyte composition according to the present invention may be mixed with one or more additional electrochemical cells comprising an electrolyte composition not according to the present invention.

[0282] On the other hand, the present invention also provides an electrolyte composition comprising a solvent system, the solvent system comprising: a first component comprising one or more non-aqueous solvents; a second component comprising one or more performance additives, the performance additives comprising a sulfur-containing compound; and wherein the electrolyte composition further comprises one or more metal-containing salts at a concentration of 0 mol / kg to ≤0.2 mol / kg. The electrolyte composition may be further defined as described above or according to the embodiments disclosed herein.

[0283] On the other hand, the present invention also provides an electrolyte composition comprising a solvent system, wherein the solvent system comprises: a first component comprising one or more non-aqueous solvents; a second component comprising one or more performance additives selected from boron-containing compounds and surfactants, the amount of which is >0.5% to ≤10% by weight of the solvent system; wherein the electrolyte composition further comprises one or more metal-containing salts at a concentration of 0 mol / kg to ≤0.2 mol / kg. The electrolyte composition may be further defined as described above or according to the embodiments disclosed herein.

[0284] In the last aspect, the present invention also provides an electrolyte composition having a solvent system, the solvent system comprising: a first component comprising one or more non-aqueous solvents; a second component comprising one or more performance additives selected from sulfur-containing compounds, boron-containing compounds and surfactants; and wherein the composition further comprises one or more metal-containing salts at a concentration of 0 mol / kg to ≤0.2 mol / kg. The electrolyte composition may be further defined as described above or according to the embodiments disclosed herein. BRIEF DESCRIPTION OF THE DRAWINGS

[0286] The present invention will now be described with reference to the following drawings, in which:

[0287] Figure 1 A graph showing cathode discharge capacity (mAh / g) versus cycle number for a battery (APFC 489) using an electrolyte composition according to the present invention (sample SOL 21).

[0288] Figure 2 A graph showing the full cell voltage (V) versus cathode specific capacity (mAh / g) for the first four cycles of a battery (APFC 489) using an electrolyte composition according to the present invention (Sample SOL 21).

[0289] Figure 3 A graph showing the relationship between the full cell voltage (V) and the cathode specific capacity (mAh / g) of a battery (APFC 489) using the electrolyte composition according to the present invention (sample SOL 21) starting from the 5th cycle.

[0290] Figure 4 A graph showing the relationship between full cell voltage (V) and cathode specific capacity (mAh / g) is shown, which shows the rate performance at different C rates from the 3rd to the 10th cycle of a battery (APFC 488) using the electrolyte composition of the present invention (sample SOL 21).

[0291] Figure 5 A graph showing cathode discharge capacity (mAh / g) versus cycle number for a battery (APFC 488) using an electrolyte composition according to the present invention (sample SOL 21).

[0292] Figure 6 A graph showing the relationship between the full cell voltage (V) and the cathode specific capacity (mAh / g) of a battery (APFC 488) using the electrolyte composition according to the present invention (sample SOL 21) starting from the 11th cycle.

[0293] Figure 7 A graph showing cathode capacity (mAh / g) versus cycle number for a battery (APFC 475) using an electrolyte composition according to the present invention (sample SOL 21).

[0294] Figure 8 A graph of cathode discharge capacity (mAh / g) versus cycle number is shown to illustrate the cycling stability of a cell (APFC 489) using an electrolyte composition according to the present invention (sample SOL 21) compared to the cycling stability of a cell (APFC 492) using a control electrolyte composition (sample TEL 67a).

[0295] Fig. 9 A graph of the relationship between full cell voltage (V) and cathode discharge capacity (mAh / g) at the 3rd cycle is shown to illustrate the battery (APFC 489) using the electrolyte composition according to the present invention (sample SOL 21) compared to the battery (APFC 492) using the control electrolyte composition (sample TEL 67a).

[0296] Fig.10 A graph of the relationship between full cell voltage (V) and cathode discharge capacity (mAh / g) at the 6th cycle is shown to illustrate the battery (APFC 489) using the electrolyte composition according to the present invention (sample SOL 21) compared to the battery (APFC 492) using the control electrolyte composition (sample TEL 67a).

[0297] Fig.11 A graph showing the full cell voltage (V) versus cathode specific capacity (mAh / g) for the first four cycles of a cell (APFC 485) using an electrolyte composition according to the present invention (sample SOL 14w).

[0298] Fig.12 A graph showing cathode discharge capacity (mAh / g) versus cycle number for a battery (APFC 485) using an electrolyte composition according to the present invention (sample SOL 14w).

[0299] Fig.13 A graph showing the full cell voltage (V) versus cathode specific capacity (mAh / g) for the first four cycles of a cell (APFC 491) using an electrolyte composition according to the present invention (sample SOL 9c).

[0300] Fig.14 A graph showing cathode discharge capacity (mAh / g) versus cycle number for a cell (APFC 485) using an electrolyte composition according to the present invention (sample SOL 14w) compared to other cells (APFC 491) using another electrolyte composition according to the present invention (sample SOL 9c).

[0301] Fig.15 A graph showing cathode discharge capacity (mAh / g) versus cycle number for a cell (APFC 489) using an electrolyte composition according to the present invention (Sample SOL 21) compared to other cells (APFC 490) using another electrolyte composition according to the present invention (Sample SOL 21a).

[0302] Fig.16 A graph showing the cathode discharge (mAh / g) capacity versus cycle number for a battery (APFC 487) using an electrolyte composition according to the invention (sample SOL 16h).

[0303] Fig.17 A graph showing the full cell voltage (V) versus cathode specific discharge capacity (mAh / g) for the first two cycles of a cell (APFC 487) using an electrolyte composition according to the present invention (sample SOL 16h).

[0304] Fig.18 A graph showing the relationship between the full cell voltage (V) and the cathode discharge capacity (mAh / g) at the 12th, 30th and 61st cycles of a battery (APFC 487) using an electrolyte composition according to the present invention (sample SOL 16h).

[0305] Fig.19 A graph of full cell voltage (V) versus cathode discharge capacity (mAh / g) is shown to illustrate the cycling performance of an anode-free sodium battery using an electrolyte composition according to the present invention (SOL 21c).

[0306] Fig. 20A graph showing the full cell voltage (V) versus cathode discharge capacity (mAh / g) for a cell (APFC 497) using a control electrolyte composition (Sample TEP).

[0307] Fig.21 A graph showing the full cell voltage (V) versus cathode discharge capacity (mAh / g) for a cell (APFC 498) using a control electrolyte composition (Sample TEP).

[0308] Fig. 22 A graph showing the full cell voltage (V) versus cathode discharge capacity (mAh / g) for cells using an electrolyte composition according to the present invention (samples SOL 21d; SOL 21e; ​​SOL 21f; SOL 21 and SOL 21h) compared to a control electrolyte composition (sample TEP).

[0309] Fig.23 A graph showing the full cell voltage (V) versus cathode discharge capacity (mAh / g) for cells using an electrolyte composition according to the present invention (samples SOL 21d and SOL 21g) compared to a control electrolyte composition (sample TEP).

[0310] Fig.24 A graph showing the cathode discharge capacity (mAh / g) versus cycle number for cells APFC 488 and APFC 514 using an electrolyte composition according to the present invention (sample SOL 21).

[0311] Fig.25 A graph showing the relationship between the full cell voltage (V) and the cathode discharge capacity (mAh / g) of a battery (APFC 518) using an electrolyte composition according to the present invention (sample TEL 84) compared to other batteries (APFC489) using an electrolyte composition according to the present invention (sample SOL 21).

[0312] Fig.26 A plot showing the full cell voltage (V) versus cathode discharge capacity (mAh / g) for a cell (APFC 497) using a control electrolyte composition (sample TEP) compared to other cells (APFC 531) using a control electrolyte composition (sample TEL 84a).

[0313] Fig. 27 A graph showing the relationship between the full cell voltage (V) and the cathode discharge capacity (mAh / g) of a battery (APFC 527) using an electrolyte composition not according to the present invention (sample TEL 82) compared to other batteries (APFC528) using an electrolyte composition according to the present invention (sample SOL 21).

[0314] Fig.28 A graph showing cathode discharge capacity (mAh / g) versus cycle number for a cell (APFC 542) using an electrolyte composition according to the present invention (sample SOL 25a) compared to cells (APFC541; APFC551) using a control electrolyte composition (samples SOL 25; LP 30).

[0315] Fig.29 A graph showing the relationship between the full cell voltage (V) and the cathode discharge capacity (mAh / g) of batteries (APFC 488; APFC 547; APFC 548) using the electrolyte composition according to the present invention (samples SOL 21; TEL 80f; TEL 80g). Example

[0316] The electrolyte compositions studied were prepared using the following general procedure: Appropriate amounts of the first component (e.g., a solvent for the desired solvent system) and the second component (e.g., the correct amount of one or more performance additives) were weighed out in an argon-filled glove box and added to a brown or clear glass bottle. To thoroughly dry the formed solvent, 4Å molecular sieves (Sigma-Aldrich) were added and the solvent mixture was allowed to dry for at least 24 hours. The electrolyte composition was then prepared for use and stored in an argon-filled glove box. For those compositions containing metal salts (according to the present invention or otherwise), the desired weight of (multiple) salts was added to another bottle (a transparent or brown glass bottle or a container made of a selected material such as polypropylene, PTFE, stainless steel, etc.), to which the desired amount of the solvent mixture was added. The electrolyte was then stirred via magnetic particles or a mechanical stirrer for any time from 5 minutes to 100 hours, or alternatively, the (multiple) salts were naturally dissolved in the electrolyte by simply leaving the bottle / container still, or by mechanically shaking the bottle / container in an accelerated manner.

[0317] The exact composition of each electrolyte composition studied is detailed in Table 1 below:

[0318] Table 1

[0319]

[0320] For the avoidance of doubt, the concentrations expressed as "m" (mass molar concentration) above refer to the total moles of metal salts per 1 kg or 1000 g of the solvent system. Alternatively, the concentrations expressed as "M" (mass molar concentration) above refer to the total moles of metal salts per liter of the solvent system.

[0321] Abbreviations used :

[0322] EC = ethylene carbonate, DEC = diethyl carbonate, PC = propylene carbonate, FEC = fluoroethylene carbonate, PCS = 1,3-propylene glycol cyclic sulfate, P123 = Pluronic P123, TEP = triethyl phosphate, TMSB = tris(trimethylsilyl)borate, tetraglyme = tetraethylene glycol dimethyl ether, diglyme = diethylene glycol dimethyl ether, VC = vinylene carbonate, DMC = dimethyl carbonate.

[0323] Please note that in Table 1 above, the weight % of various solvents and / or performance additives are relative to the total weight of the solvent system.

[0324] Battery structure

[0325] General procedure for making hard carbon sodium-ion batteries

[0326] Examples 1 to 4 herein relate to experimental device characterization of small sodium-ion pouch cells with a nominal capacity of about 4 to 7 mAh.

[0327] Sodium-ion batteries are made using a mixed-phase O3 / P2 oxide cathode, a hard carbon anode, and an electrolyte (as appropriate). Aluminum sheets are attached to each electrode and the battery is housed in a polymer-coated aluminum bag.

[0328] The positive (cathode) electrode is made by solvent casting a slurry of active material, conductive carbon, binder and solvent using a doctor blade method. The conductive carbon used is C65 (Imerys). PVdF copolymer (e.g. W#7500 from Kureha Chemicals) is used as a binder and N-methylpyrrolidone (NMP) is used as a solvent. The slurry is then cast onto a carbon-coated aluminum foil and dried at about 120°C under vacuum. The electrode film contains the following components (expressed in weight percentage): 89% (or 92%) active material, 5% (or 4%) C65 carbon and 6% (or 4%) W#7500 binder.

[0329] The hard carbon negative (anode) electrode was prepared by doctor blade solvent casting a slurry of hard carbon active material (Kuranode Type 1, supplied by Kureha), conductive carbon, binder and solvent. The conductive carbon used was C65 (Imerys). Sodium carboxymethyl cellulose (CMC) (Aqualon from Ashland) was used. TMAQU D-5283) and a mixture of styrene-butadiene rubber (SBR) (BM-451B from Zeon Europe Gmbh) were used as binders, and water was used as solvent. The slurry was then cast onto a carbon-coated aluminum foil and dried under vacuum at about 120°C. The electrode membrane contained the following components (expressed in weight percentage): 95% active material, 1.5% C65 carbon, and 3.5% binder mixture.

[0330] After coating the cathode and anode, they are punched out to the desired dimensions.

[0331] The separator used is a typical polyolefin separator commonly used in any type of rechargeable lithium-ion or sodium-ion battery, such as Celgard 2500. The cathode / separator / anode assembly is placed in a soft bag with two aluminum-based connecting pieces as terminals in a glove box and filled with the liquid electrolyte in an amount that is typical for such type of lithium-ion or sodium-ion batteries containing polyolefin separators. These soft pack batteries are then sealed in a glove box and taken out for battery testing.

[0332] General procedure for making anode-free sodium batteries

[0333] The anode-free sodium battery described in Experiment 5 was fabricated as a pouch cell. The nominal capacity of the anode-free pouch cell was about 5 mAh. The cathode contained a mixed phase O3 / P2 layered oxide sodium ion active material mixed with C65 carbon black conductive additive and polyvinylidene fluoride (PVDF) binder in a weight ratio of 89: 06: 05 on a carbon-coated aluminum foil.

[0334] More specifically, the anode was an En' Safe 92' substrate, which is an aluminum foil coated with a thin (approximately 1 μm) carbon primer layer, and was purchased from ARMOR (its En' Safe® range of products).

[0335] The rest of the procedures for fabricating anode-free sodium batteries are the same as those for sodium-ion pouch cells described above.

[0336] General procedure for making hard carbon K-ion batteries

[0337] The K-ion battery used in this article uses a P3 type K 0.5 [Mn 0.8 Fe 0.1 Ni 0.1]O2 layer oxide cathode (whose performance has been shown previously by Choi et al. in Energy Storage Mater., 2020, 25, 714–723). The formulation of this cathode is the same as that used for the Na-ion layered O3 / P2 oxide and is coated on carbon-coated aluminum foil. The anode used in these cells is hard carbon coated on aluminum foil (the same anode used in all Na-ion battery experiments). The rest of the procedure for making the K-ion battery is the same as that for the Na-ion pouch cell described above.

[0338] General procedure for manufacturing graphite anode-based lithium-ion batteries

[0339] The Li-ion cells illustrated herein used a layered Li Ni-Mn-Co oxide cathode (NMC532) (purchased from MTI). This cathode had the same formulation as that used for the Na-ion layered O3 / P2 oxide and was coated on a carbon-coated aluminum foil. The anode used in these cells was graphite (purchased from MTI) and was coated on a copper foil. The rest of the procedure for making the Li-ion cells was the same as that for the Na-ion pouch cells described above.

[0340] Battery Test

[0341] The batteries were tested using a constant current (galvanostatic) cycling technique.

[0342] The cells were cycled between preset voltage limits at a given current density using commercial battery cyclers from MTI Inc. (Richmond, CA, USA) or Maccor (Tulsa, OK, USA). During charging, alkali ions are embedded in the carbonaceous anode material (or plated on the substrate as alkali metals for anode-free cells). During discharge, alkali ions are extracted from the anode (for anode-free cells, alkali metals are stripped from the substrate as alkali ions) and reinserted into the cathode active material.

[0343] All cells were subjected to cycling experiments at charging rates such as ±C / 5 and ±C / 10 (or other rates such as ±C / 50 mentioned for each experiment). Rate performance testing also observed discharge rates of C / 5, C / 10, 1C, and 2C. All cells were rested for 4-24 hours before cycling. Table 2 provides an overview of the conditions for each experiment.

[0344] Table 2 – Overview of cycling experiments

[0345]

[0346]

[0347]

[0348]

[0349] Example 1A - Cycling Performance of Cells Using Electrolyte Compositions Containing Triethyl Phosphate Solvent and One or More Performance Additives

[0350] Using the general method for preparing hard carbon sodium-ion batteries discussed above, a test pouch cell (APFC 489) was prepared with electrolyte composition SOL 21. The cycling performance of the cell was then tested by cycling studies as follows:

[0351] The first 4 cycles of the battery were operated (charge / discharge) at ±C / 10 over a voltage range of 4.1 to 0 V. Figure 2 From the results shown, the Coulombic efficiency increases from 87.5% in the first cycle to 98.7% in the fourth cycle.

[0352] The cells were operated at ±C / 5 in the voltage range of 4.05 to 1.8 V from the 5th to 57th cycles. Figure 3 From the results shown, the Coulombic efficiency was maintained at 99.4% to 99.5% from the 6th to the 54th cycle (see the results of the 6th, 10th and 54th cycles).

[0353] Overall, the cell exhibited good cycling stability, retaining 91% of the cathode discharge capacity over 53 ±C / 5 cycles, as shown in Figure 2. Figure 1 shown.

[0354] Thus, good cycling performance in terms of stability and discharge capacity retention was obtained using an electrolyte composition that was substantially free of one or more alkali metal salts (eg, NaPF6 according to Example 2 below).

[0355] Example 1B - Rate Performance of Cells Using Electrolyte Compositions Containing Triethyl Phosphate Solvent and One or More Performance Additives

[0356] Using the general method for preparing hard carbon sodium-ion batteries discussed above, a test pouch cell (APFC 488) was prepared using electrolyte composition SOL 21. The rate performance of the cell was then tested by cycling studies as follows:

[0357] The first two cycles of the cell were run (charge / discharge) at ±C / 10 between the voltage range of 4.1 to 0 V. The rate performance was evaluated for cycles 3 to 10 run between the voltage range of 4.05 to 1.8 V. During these cycles, the cell was first charged always at C / 5. Subsequently, each pair of cycles, 3-4, 5-6, 7-8, and 9-10, was discharged at different rates of C / 5, C / 2, 1C, and 2C, respectively.

[0358] Figure 5The capacity is shown to be dependent on the number of cycles, with good reversibility up to C / 2. Figure 4 From the rate performance results shown, the cell discharged up to C / 2 showed minimal polarization, so the cell discharged at C / 2 retained 92% of the cathode specific capacity, while the cell discharged at C / 5 retained 100% of the cathode specific capacity. Thus, good rate performance is obtained using an electrolyte composition that is substantially free of one or more alkali metal salts.

[0359] like Figure 4 More clearly shown, the cells discharged at 1C and 2C rates retained less than 50% of the cathode specific capacity (i.e., at 1C = 48% cathode specific capacity; at 2C = 1.4% cathode specific capacity).

[0360] The cells were then subjected to further cycling at ±C / 5 between voltages of 4.05 and 1.8 V from cycle 11 up to cycle 72. Figure 6 From the results shown, the Coulombic efficiency was maintained at 99.4% to 99.6% from the 12th cycle to the 70th cycle (see the results of the 12th, 20th, 26th and 70th cycles). In addition, the battery maintained a high capacity retention rate of more than 90% compared to the 11th cycle, as shown in Figure 2. Figure 6 As shown, it exhibits overall good stability and discharge capacity.

[0361] Therefore, it is expected that the sodium ion battery is preferably cycled at a rate of about C / ≥2, more preferably C / ≥5 when using an electrolyte composition that is substantially free of one or more alkali metal salts.

[0362] Example 1C - Long-term Cycling Stability of Batteries Using Electrolyte Compositions Containing Triethyl Phosphate Solvent and One or More Performance Additives

[0363] Using the general method for preparing hard carbon sodium-ion batteries discussed above, a test pouch cell (APFC 475) was prepared with electrolyte composition SOL 21. The long-term cycling stability of the test cell was then investigated over 221 cycles as follows:

[0364] The first two cycles of the cell were run (charge / discharge) at ±C / 5 between the voltage range of 4.1 to 0 V. Then, cycles 3 to 120 were run at ±1C (C / 1) between the voltage range of 4.05 to 1.8 V. Finally, cycles 121 to 221 were run in the same voltage range as cycles 3 to 120, but at a rate of ±C / 5.

[0365] Figure 7It is shown that the capacity decay of the cathode from the 121st to the 221st cycle was only about 19% (relative to the capacity output at the 121st cycle). Therefore, good long-term cycling performance in terms of stability and discharge capacity retention is obtained using an electrolyte composition that is substantially free of one or more alkali metal salts.

[0366] Similar to the conclusion of Experiment 1B, Figure 7 It can be seen that the delivered capacity at the C / 1 rate is much lower than the delivered capacity at the C / 5 rate (about 72.8 mAh / g): at the C / 1 rate, the output capacity of the battery first decreases from 33.9 mAh / g in the 3rd cycle to 11.3 mAh / g in the 5th cycle, but then steadily increases to 18.9 mAh / g in the 120th cycle, proving that the battery can be reversibly cycled at faster cycle rates such as C / 1, albeit with lower capacity.

[0367] Therefore, it is expected that the sodium ion battery is preferably cycled at a rate of about C / ≥2, more preferably C / ≥5 when using an electrolyte composition that is substantially free of one or more alkali metal salts.

[0368] Example 2 - Comparison between a cell according to the invention and a cell using an electrolyte comprising a carbonate electrolyte, one or more performance additives and NaPF6 salt (ie not according to the invention).

[0369] The comparative electrolyte composition TEL 67a was prepared according to the disclosure of international patent application PCT / GB2020 / 051317 published as WO2020 / 240209A1.

[0370] Using the general method for preparing hard carbon sodium ion batteries discussed above, a test pouch cell (APFC 492) was prepared using electrolyte composition TEL 67a. The cycling performance of the test cell was then studied and the results were compared with the test cell APFC 489 discussed in Example 1A above.

[0371] Both APFC 492 and APFC 489 were operated (charge / discharge) at ±C / 10 between the voltage range of 4.1 and 0 V for 4 cycles. Figure 8 The capacity versus cycle number relationship is shown, and at C / 10, there is good reversibility of the cathode sodium ions.

[0372] From the 5th to the 57th cycle, both APFC 492 and APFC 489 were operated at ±C / 5 in the voltage range of 4.05 to 1.8 V. Figure 8 Similarly, good reversibility is shown for the presence of cathode sodium ions at C / 5.

[0373] Surprisingly, at ±C / 5 and ±C / 10 rates, APFC 489 (according to the invention) delivers comparable capacity to APFC 492 (not according to the invention). In fact, the cycling stability of APFC 489 is particularly comparable to that of APFC 492 over the first 50+ cycles.

[0374] In more detail, Fig. 9 and 10 The cell voltage versus cathode specific capacity at the 3rd cycle ±C / 5 and the 6th cycle ±C / 10 for APFC 489 and APFC 492 are shown, respectively. From the results, the polarization degree of APFC 489 is only slightly higher at both the ±C / 10 rate and the ±C / 5 rate compared to the corresponding cycles of APFC 492 using TEL 67a. This is reflected in the close mid-capacity voltage hysteresis values ​​for the two cells:

[0375] like Fig. 9 As shown, at ±C / 10, the mid-capacitance voltage hysteresis for APFC 489 and APFC 492 is 120 mV versus 101 mV, respectively, resulting in a 19 mV difference.

[0376] At ±C / 5, the mid-capacitance voltage hysteresis for APFC 489 and APFC 492 was 210 mV versus 143 mV, respectively, resulting in a 67 mV difference.

[0377] Therefore, compared to a hysteresis value of 67 mV at ±C / 5, the hysteresis value at ±C / 10 is only 19 mV.

[0378] Fig. 9 and Fig.10 It is further shown that the round-trip energy efficiency (RTEE) differences of the two cells are similar (i.e., about 1.2% at ±C / 10= and about 2.2% at ±C / 5).

[0379] Thus, the cycling performance in terms of stability, RTEE, and output capacity obtained from an electrolyte composition that is substantially free of one or more alkali metal salts can be substantially similar to the cycling performance of electrolyte compositions taught in the prior art (containing a large amount of one or more alkali metal salts), especially at rates such as C / ≥5, or more preferably C / ≥10.

[0380] Example 3A - Cycling and long-term cycling performance of cells using electrolyte compositions containing carbonate solvents and one or more performance additives

[0381] Using the general method for preparing hard carbon sodium-ion batteries discussed above, a test pouch cell (APFC 485) was prepared using the electrolyte composition SOL 14w. The cycling performance of the cell was then tested by cycling studies as follows:

[0382] The first four cycles were run at ±C / 10 in the voltage range of 4.1 to 0 V. The Coulombic efficiency of the first four cycles increased from 61.9% in the first cycle to 87.9% in the fourth cycle, as shown in Fig.11 as shown (note that the first charge was stopped early due to human error, as indicated by the arrow).

[0383] The 5th cycle was run at ±C / 5 over the voltage range of 4.05 V to 1.8 V to over 250 cycles. Fig.12 Shows some evidence of reversible cycling at ±C / 5.

[0384] Therefore, cycle performance in terms of stability and discharge capacity retention is achieved using an electrolyte composition that is substantially free of one or more alkali metal salts.

[0385] The results also show that it is particularly desirable that the sodium ion battery discharge preferably at a rate of about C / ≥10 when using an electrolyte composition comprising a carbonate-containing solvent that is substantially free of one or more alkali metal salts.

[0386] Example 3B - Cycling and long-term cycling performance of cells using electrolyte compositions containing carbonate solvents and one or more performance additives

[0387] Using the general method for preparing hard carbon sodium-ion batteries discussed above, a test pouch cell (APFC 491) was prepared using electrolyte composition SOL 9c. The cycling performance of the cell was then tested by cycling studies as follows:

[0388] The first four cycles were run at ±C / 10 in the voltage range of 4.1 to 0 V. The Coulombic efficiency of the first four cycles increased from 86.3% in the first cycle to 97.7% in the fourth cycle, as shown in Fig.13 shown.

[0389] The 5th cycle was run at ±C / 5 over the voltage range of 4.05 V to 1.8 V to over 150 cycles and compared with the results obtained for the APFC 485 of Example 3A under the same cycling conditions.

[0390] from Fig.14From the comparison results shown, higher discharge capacities were observed over 150 cycles compared to APFC 485, indicating that the EC: DEC: PC solvent system is superior to the PC-dominated solvent system of APFC 485. For example, at the 20th cycle at ±C / 5, APFC 491 using SOL 9c can deliver 31.9 mAh / g, while APFC 485 using SOL 14w has a lower 20th cycle capacity (27.8 mAh / g).

[0391] Example 3C - Cycling Performance of Cells Using Electrolyte Compositions Containing a Carbonate Solvent in Combination with Triethyl Phosphate Solvent and One or More Performance Additives

[0392] Using the general method for preparing hard carbon sodium-ion batteries discussed above, a test pouch cell (APFC 490) was prepared with electrolyte composition SOL 21a. The cycling performance of the cell was then tested by cycling studies as follows:

[0393] The first four cycles were run at ±C / 10 in the voltage range of 4.1 to 0 V. After this, the fifth cycle was run at ±C / 5 in the voltage range of 4.05 to 1.8 V for more than 75 cycles and compared with the results obtained for the APFC489 of Example 1A cycled under the same conditions.

[0394] according to Fig.15 The results shown, show that lower discharge capacity was observed over 75 cycles for APFC 490 compared to APFC 489, indicating that the TEP-only solvent system is preferred over the TEP-with-carbonate solvent system of APFC 489.

[0395] Example 4A - Cycling and Rate Performance of Cells Using Electrolyte Compositions Containing Glyme Solvent and One or More Performance Additives

[0396] Using the general method for preparing hard carbon sodium-ion batteries discussed above, a test pouch cell (APFC 487) was prepared using the electrolyte composition SOL 16H. The rate performance of the cell was then tested by cycling studies as follows:

[0397] The first two cycles of the battery were operated at ±C / 10 between the voltage range of 4.1 and 0 V (charge / discharge).

[0398] The rate performance was then evaluated for cycles 3 to 10 running in the voltage range of 4.05 to 1.8 V. During these cycles, the battery was first charged at C / 5. Subsequently, each pair of cycles 3-4, 5-6, 7-8, and 9-10 were discharged at different rates of C / 5, C / 2, 1C, and 2C, respectively.

[0399] The cells were then subjected to further cycling at ±C / 5 between voltages of 4.05 and 1.8 V from the 11th cycle up to 190th cycle.

[0400] Fig.16 Showing the capacity versus cycle number, at ±C / 10, there is an acceptable discharge capacity for the cathode sodium ion. However, cells discharged at C / 5, C / 2, 1C and 2C rates show much lower capacities, but nonetheless still exhibit reversible cycling.

[0401] according to Fig.17 The results shown show that at ±C / 10, the Coulombic efficiency increases from 78.2% in the 1st cycle to 93.7% in the 2nd cycle. However, at the top of the charge (from about 3.8 to 4.0 V), there are some disturbances in the cycling curves during the CV step.

[0402] according to Fig.18 The results shown show that at ±C / 5, the Coulombic efficiency drops from 100.8% at the 12th cycle to 99.7% at the 12th and 61st cycles. Fig.17 Similarly, there are some disturbances in the cycling curves at the charge top of the CV step.

[0403] Conclusions from Examples 1 to 4

[0404] Examples 1-4 demonstrate the surprising result that sodium-ion batteries can be effectively cycled with liquid electrolytes that do not contain any salt. The collected data show that sodium-ion batteries with salt-free electrolytes can show good cycling performance at rates of C / 2 and slower: such rates are ideally suited for stationary energy storage applications where the battery is expected to be discharged over several hours, such as at C / 5 or even C / 20.

[0405] Clearly, the electrolyte composition is critical to maintaining good cycling stability comparable to existing high-performance salt-based cells. The results indicate that TEP is the best solvent. However, carbonate-containing solvents and glyme-containing solvents also still exhibit varying degrees of performance (good capacity, efficiency, cycling stability, and rate capability), which is itself a very unexpected result. These experiments also point to the importance of additives, especially SEI-forming additives, and Experiment 6 below provides further details on their importance.

[0406] Example 5 - Cycling and rate performance of an anode-free sodium battery using the electrolyte composition of the present invention

[0407] Using the general method for preparing anode-free sodium batteries discussed above, test cells (INFC 46) were prepared with electrolyte composition SOL 21c. The rate performance of the test cells was then studied by cycling at ±C / 10 between voltages of 4.0 and 1.0 V.

[0408] from Fig.19 From the results shown, the battery INFC 46 using the electrolyte composition SOL 21c shows cycling reversibility. Specifically, the INFC 46 can output a specific capacity of 64.7 mAh / g in the first cycle, thus demonstrating reversibility.

[0409] Therefore, the results of Example 5 lead to the following conclusion: the composition according to the present invention has practical application in anode-free sodium batteries as well as sodium-ion batteries.

[0410] Example 6

[0411] This experiment further studies the cycling performance of hard carbon sodium ion batteries using the electrolyte composition according to the present invention. The purpose of this experiment is to study the importance of the specific type and amount of additives in the salt-free electrolyte on the performance of sodium ion batteries.

[0412] No additives

[0413] Cells APFC 497 and APFC 498 were cycled with 100 wt % TEP and cycled at ±C / 10 between voltages of 4.1 to 0 V. Both cells were also cycled between voltages of 4.1 to 0 V at ±C / 50.

[0414] like Fig. 20 and 21 As shown, both APFC 497 and APFC 498 polarize momentarily and show negligible capacity when cycled at ±C / 10. However, when cycled at ±C / 50, the output capacity is unexpectedly higher; for example, the ±C / 50 capacity of APFC 497 is 24 mAh / g and that of APFC 498 is 23 mAh / g (the charging of this cell is timed to 3.90 V without a subsequent CV step), despite the fact that the cell was only charged to 3.68 V (the charging step of the cell was timed to cut off, after which the cell cycler automatically entered a CV step at 4.1 V for 5 seconds, which then also cut off naturally),

[0415] Experiments have shown that reversible cycling of sodium-ion batteries can be achieved using an electrolyte composition that is substantially free of one or more metal-containing salts.

[0416] Boron-containing additives

[0417] Cell APFC 505 was cycled between 4.1 and 0 V at ±C / 10 using TEP containing 1 wt % TMSB (sample SOL 21d).

[0418] Cell APFC 509 was cycled between 4.1 and 0 V at ±C / 10 using TEP containing 5 wt % TMSB (sample SOL 21 g).

[0419] like Fig. 22 As shown, the APFC 505 cell achieved a charge capacity of 8.8 mAh / g at cycle 4, and a discharge capacity of 7.5 mAh / g. It can be seen that these output capacities at ±C / 10 are much higher than those seen by the Na-ion pouch cells containing only TEP solvent as described on the previous page (the cycling curves for APFC 497 are also shown in Fig. 22 superior).

[0420] Fig.23 The first cycle curves at ±C / 10 for sodium-ion cells using a salt-free dielectric without any additives (APFC 497 with TEP) or with a B-additive (AFPC 505 with SOL 21d or APFC 509 with SOL 21g) are shown. It can be seen that the presence of the TMSB additive has a significant effect on the charge cycle, regardless of the amount: APFC 497 polarizes immediately to 4.1 V during the CC step (with a capacity of only 0.04 mAh / g during the charge CC step), while the two TMSB-containing cells deliver significantly higher capacities during the CC step (APFC 505 delivers 72.1 mAh / g and APFC 509 delivers 86.9 mAh / g during the CC charge step). The effect on discharge capacity is also significant, although not as large as that during the charge step: the first cycle discharge capacity is 2.8 mAh / g for APFC 497, 13.7 mAh / g for APFC 505, and 0.9 mAh / g for APFC 509.

[0421] This experiment demonstrates the unexpected performance of using a boron-containing additive (TMSB) in an electrolyte composition that is substantially free of one or more metal-containing salts. Specifically, when TMSB is used as the sole additive, it can result in significantly higher discharge capacities of Na-ion cells at rates such as C / 10 compared to an electrolyte composition that is substantially free of one or more metal-containing salts and does not contain any additives (i.e., 100% TEP).

[0422] Surfactant Additives

[0423] Cell APFC 506 was cycled between voltages of 4.1 and 0 V at ±C / 10 using TEP containing 1 wt % P123 (sample SOL 21e).

[0424] like Fig. 22 As shown, it can be seen that when cycled at ±C / 10, APFC 506 performs similarly to the benchmark APFC 497 cell: the former has a fourth cycle discharge capacity of 1.62 mAh / g, while the latter has a fourth cycle discharge capacity of 1.64 mAh / g. Thus, this experiment demonstrates the unexpected performance of using a surfactant (P123) in an electrolyte composition that is substantially free of one or more metal-containing salts.

[0425] Sulfur-containing additives

[0426] Cell APFC 508 was cycled between 4.1 and 0 V at ±C / 10 using TEP containing 5 wt % PCS (sample SOL 21f).

[0427] like Fig. 22 As shown, the APFC 508 cell yielded significantly higher capacities than those obtained from other cells containing other types of single additives: 108.7 mAh / g charge capacity and 107.3 mAh / g discharge capacity at cycle 4. This experiment demonstrates the unexpected performance of using a sulfur-containing additive (PCS) in an electrolyte composition that is substantially free of one or more metal-containing salts.

[0428] Combination of additives

[0429] TEP containing 5 wt % PCS, 1 wt % P123, 5 wt % TMSB (sample SOL 21 h) was cycled between 4.1 and 0 V at ±C / 10.

[0430] like Fig. 22 As shown, the battery APFC 510 obtained a charge capacity of 110.7 mAh / g and a discharge capacity of 109.2 mAh / g in the 4th cycle.

[0431] Similarly, TEP containing 5 wt % PCS, 1 wt % P123, 1 wt % TMSB (sample SOL 21) was cycled between 4.1 and 0 V at ±C / 10.

[0432] like Fig. 22 As shown, battery APFC 489 obtained a charge capacity of 112.3 mAh / g and a discharge capacity of 110.8 mAh / g in the 4th cycle.

[0433] As can be seen, both cells performed significantly better than a baseline cell (APFC 497) that did not contain any additives.This experiment demonstrates the unexpected performance of using a combination of additives in an electrolyte composition that is substantially free of one or more metal-containing salts.

[0434] in conclusion

[0435] As can be seen above, different types of additives have different effects on the performance of sodium ion batteries using electrolytes that are substantially free of one or more metal salts.

[0436] In addition, APFC 489 and APFC 510 cells each exhibited higher or similar performance capacity than APFC 505, APFC 506, and even APFC 508 cells using B-containing additives, surfactant-containing additives, and S-containing additives, respectively, alone. This synergistic performance of the combination of additives in providing desirable cell properties in an electrolyte composition that is substantially free of one or more metal-containing salts is highly unexpected.

[0437] The results for each of these additives (S-containing, B-containing, and surfactant-containing) are indeed surprising, as the absence of a salt causing transient polarization would normally be expected to override all subsequent effects of any such additive.

[0438] Example 7

[0439] This experiment studies the cycling performance of hard carbon sodium ion batteries using the electrolyte composition according to the present invention and different polyolefin separators.

[0440] Two different polyolefin separators were investigated in cells cycled using TEP (sample SOL 21) containing 5 wt% PCS, 1 wt% P123, 1 wt% TMSB:

[0441] • Cell APFC 488 (according to Experiment 1B) using a polyolefin separator with a thickness of 25 μm; and

[0442] • The APFC 514 battery uses a polyolefin separator with a thickness of 16 μm.

[0443] The first two cycles of APFC 488 and APFC 514 were run at ±C / 10 (charge / discharge) between the voltage range of 4.1 to 0 V. The rate performance was evaluated for the 3rd to 10th cycles run between the voltage range of 4.05 to 1.8 V. During these cycles, the cells were always charged at a C / 5 rate. Subsequently, each pair of cycles, 3-4, 5-6, 7-8, and 9-10, were discharged at different rates of C / 5, C / 2, 1C, and 2C, respectively. After these cycles, starting from the 11th cycle, the cells were placed at 4.05-1.8 V for ±C / 5 cycling.

[0444] Fig.24 The capacity versus cycle number relationship is shown, with good reversibility of the cathode sodium ions for both APFC 488 and APFC 514 up to C / 2. It can be seen that the discharge capacity of APFC 514 at 1C rate is significantly higher with the 16 µm separator than with the 25 µm separator at 1C rate: the former cell outputs about 79 mAh / g, while the latter can only output about 46 mAh / g. Similarly, the discharge capacity of APFC 514 at 2C rate is significantly higher with the 16 µm separator than with the 25 µm separator at 2C rate: the former cell outputs about 23 mAh / g, while the latter can only output about 1.3 mAh / g.

[0445] It can therefore be seen that the APFC 488 discharged at 1C and 2C rates retains less than 50% of the cathode specific capacity (i.e. at 1C = 48% cathode specific capacity; at 2C = 1.4% cathode specific capacity).

[0446] In contrast, the APFC 514 discharged at 1C retained over 50% of the cathode specific capacity (i.e. at 1C = 84.2% cathode specific capacity). In addition, the APFC 514 discharged at 2C retained approximately 25% of the cathode specific capacity relative to the C / 5 capacity.

[0447] Thus, by reducing the thickness of the polyolefin separator from 25 μm to 16 μm, it is possible to improve the rate capability of a sodium ion battery using an electrolyte composition that is substantially free of one or more alkali metal salts.

[0448] Example 8

[0449] This experiment aims to study the effect that "supporting salt" may have on the electrochemical performance of sodium ion batteries using the electrolyte composition according to the present invention. For the purpose of this disclosure, "supporting salt" is any salt that is not a metal-containing salt but promotes the transfer of metal cations (i.e., Na+) from the cathode to the anode and vice versa. However, the supporting salt does not participate in the electrochemical process of the electrochemical cell.

[0450] As discussed below, the cycling performance of two Na-ion batteries was investigated at ±C / 10 between voltages of 4.1 and 0 V. Tetrabutylammonium hexafluorophosphate, or TBAPF6, was used as the supporting salt.

[0451] TEL 84

[0452] Cell APFC 518 was cycled between voltages of 4.1 and 0 V at ±C / 10 with TEP containing 1 m TBAPF6, 5 wt% PCS, 1 wt% P123, 1 wt% TMSB (sample TEL 84).

[0453] Fig.25 The results for cell APFC 518 were compared with those for cell APFC 489, which was cycled using SOL 21 as in Experiment 1A.

[0454] As shown, the addition of 1 m TBAPF6 to SOL 21 to form TEL 84 does not significantly affect the electrochemical performance of the cell. For example, APFC 489 achieved a discharge capacity of 112.9 mAh / g in the first cycle, compared to 107.5 mAh / g for APFC 518 in the first cycle.

[0455] TEL 84a

[0456] The cell APFC 513 was cycled between 4.1 and 0 V at ±C / 10 with 1 m TBAPF6 in TEP (sample TEL 84a).

[0457] Fig.26 The results for cell APFC 513 were compared with those for cell APFC 497, which was cycled according to Experiment 6A with 100 wt % TEP.

[0458] As shown, the addition of 1 m TBAPF6 to TEP to form TEL 84a surprisingly improves the electrochemical performance of the cell. For example, APFC487 achieved a discharge capacity of 1.6 mAh / g in the first cycle, compared to 54.2 mAh / g in the first cycle for APFC 518.

[0459] in conclusion

[0460] A battery cycled using the supporting salt contained in the electrolyte composition according to the present invention shows higher or similar discharge capacity performance compared to a battery without such supporting salt.

[0461] Example 9

[0462] This experiment studies the cycling performance of a hard carbon potassium ion battery using the electrolyte composition according to the present invention.

[0463] The potassium ion battery APFC 527 was prepared using the general method discussed above and cycled between voltages of 4.1 and 0 V at ±C / 5 using TEP containing 5 wt % PCS, 1 wt % P123, and 1 wt % TMSB (sample SOL 21).

[0464] Cell APFC 528 was similarly prepared using the general method discussed above and cycled between 4.1 and 0 V at ±C / 4 using TEP containing 1 m KPF6, 5 wt% PCS, 1 wt% P123, 1 wt% TMSB (sample TEL82).

[0465] Fig. 27 The cycling results of cell APFC 527 were compared to cell APFC 528. As shown, APFC 527 achieved a discharge capacity of 36.2 mAh / g at the first cycle, compared to 46.1 mAh / g for APFC 528 at the first cycle.

[0466] in conclusion

[0467] The results of Example 9 lead to the conclusion that the electrolyte composition according to the present invention has practical application in potassium ion batteries as well as sodium ion batteries and anode-free sodium batteries.

[0468] Example 10

[0469] This experiment studies the cycling performance of a lithium-ion battery based on a graphite anode using the electrolyte composition according to the present invention.

[0470] Using the general method discussed above to prepare lithium ions, the following cells were fabricated: APFC 541 with a salt-free electrolyte SOL 25 (EC: DMC = 1: 1 wt / wt); APFC 542 with a salt-free electrolyte SOL 25a (EC: DMC = 1: 1 wt / wt, which contains 5 wt% PCS, 1 wt% P123, 1 wt% TMSB); and APFC 551 with a lithium metal salt-containing LP 30 electrolyte (EC: DMC containing 1M LiPF6, EC: DMC = 1: 1 volume / volume). These three cells were cycled at ±C / 10 between 4.3 and 3V for 10 cycles.

[0471] Fig.28The cycling results of the three batteries are compared. It can be seen that the APFC 542 battery using the salt-free electrolyte (SOL25a) according to the present invention is significantly better than the other batteries. For example, the first and tenth discharge capacities of APFC 542 are 153.2 mAh / g and 150.8 mAh / g, respectively, while the values ​​of APFC541 using the additive-free salt-free electrolyte are 0 mAh / g and 0 mAh / g, respectively, and the values ​​of APFC 551 using the metal-containing electrolyte are 0 mAh / g and 0 mAh / g, respectively.

[0472] in conclusion

[0473] The results of Example 10 show that the electrolyte composition according to the present invention has utility in lithium ion batteries, as well as sodium ion batteries, potassium ion batteries, and anode-free sodium batteries. The additives in SOL 25a have never been tested in a battery without salt, so it is surprising and unexpected that there is actually a benefit to using SOL25a compared to SOL25 and LP30.

[0474] Embodiment 11

[0475] The purpose of this experiment was to investigate the effect of a minimum amount of metal-containing salt on the electrochemical performance of a sodium ion battery using the electrolyte composition according to the present invention.

[0476] As discussed below, the cycling performance of two sodium-ion batteries at ±C / 10 between voltages of 4.1 and 0 V was studied using very small amounts of NaPF6 salt at different concentrations in a TEP solvent system containing 5 wt% PCS, 1 wt% P123, and 1 wt% TMSB:

[0477] Cell APFC547 was cycled at ±C / 10 between voltages of 4.1 and 0 V with TEP containing 0.1 m NaPF6, 5 wt% PCS, 1 wt% P123, 1 wt% TMSB (sample TEL80f).

[0478] Cell APFC548 was cycled at ±C / 10 between voltages of 4.1 and 0 V with TEP containing 0.05 m NaPF6, 5 wt% PCS, 1 wt% P123, 1 wt% TMSB (sample TEL80g).

[0479] Fig.29The results for cells APFC 547 and APFC 548 were compared to the results for cell APFC 488, which was cycled using SOL 21 as in Experiment 1B. As shown, the addition of 0.1 m or 0.05 m NaPF6 to SOL 21 to form TEL 80f and TEL 80g, respectively, did not significantly affect the electrochemical performance of the cells. For example, a discharge capacity of 116.1 mAh / g was obtained for APFC 547 and 115.5 mAh / g was obtained for APFC 548 at the first cycle, compared to a discharge capacity of 113.4 mAh / g for APFC 488 at the first cycle.

[0480] in conclusion

[0481] Batteries cycled with trace amounts of metal-containing salts included in the electrolyte compositions according to the present invention show higher or similar discharge capacity performance than batteries without any metal-containing salts. This is a particularly surprising and unexpected result, as batteries with such low concentrations of salts would not be expected to produce such desired results simply by including additives.

[0482] Example 12

[0483] This experiment studies the effect of the density of a liquid electrolyte made according to the present invention compared to the density of a liquid electrolyte containing a large amount of metal salt.

[0484] For this purpose, the following two electrolytes were investigated:

[0485] SOL 14w (according to the invention): PC containing 20 wt% DEC, 2 wt% PCS, 1 wt% TMSB and 1 wt% P123.

[0486] TEL 67a (not according to the invention): PC containing 1 m NaPF6, 20 wt% DEC, 2 wt% PCS, 1 wt% TMSB, 1 wt% P123.

[0487] To measure the density of the electrolytes, 25 mL of each electrolyte was weighed. Three measurements were obtained for each electrolyte. A summary of the results obtained along with the standard deviation is shown in Table 3 below:

[0488] Table 3

[0489] Electrolyte composition sample number <![CDATA[Density of the first measurement (g / cm 3 ).]]> <![CDATA[Density of the second measurement (g / cm 3 )]]> <![CDATA[Density of the third measurement (g / cm 3 )]]> <![CDATA[Average density (g / cm 3 )]]> Standard Deviation (%) SOL 14w (according to the invention) 1.141 1.154 1.156 1.151 0.76 TEL 67a (not according to the invention) 1.268 1.27 1.265 1.268 0.21

[0490] As can be seen from Table 3, TEL 67a (not according to the invention) is about 10% heavier than SOL 14w (according to the invention). This experiment demonstrates that the electrolyte according to the invention will result in a lighter battery than those containing a large amount of salt, thereby increasing the specific energy (Wh / kg) of the resulting battery, which is a very commercially advantageous property.

[0491] The subject matter covered by the following numbered embodiments also forms part of the present invention, optionally in combination with the subject matter described above and / or defined in the following claims.

[0492] Numbered implementation scheme 1

[0493] Use of a composition comprising a solvent system as an electrolyte, the solvent system comprising:

[0494] A first component comprising one or more non-aqueous solvents;

[0495] a second component comprising one or more performance additives selected from the group consisting of sulfur-containing compounds, boron-containing compounds, and surfactants; and

[0496] The composition further comprises one or more metal-containing salts at a concentration of 0 mol / kg to ≤0.2 mol / kg.

[0497] Numbered implementation plan 2

[0498] The use according to numbered embodiment 1, wherein the composition is substantially free of one or more metal-containing salts.

[0499] Numbered implementation plan 3

[0500] The use according to numbered embodiment 1 or numbered embodiment 2, wherein the one or more non-aqueous solvents are selected from organic phosphate-based solvents, organic carbonate-based solvents and glyme-based solvents.

[0501] Numbered implementation scheme 4

[0502] The use according to any of numbered embodiments 1 to 3, wherein the second component comprises one or more performance additives in an amount of >0.5% to ≤10% by weight of the solvent system.

[0503] Numbered implementation plan 5

[0504] The use according to any one of numbered embodiments 1 to 4, wherein the surfactant is selected from anionic surfactants, cationic surfactants, nonionic (hydrophilic) surfactants and amphoteric (zwitterionic) surfactants.

[0505] Numbered implementation scheme 6

[0506] The use according to numbered embodiment 5, wherein the surfactant comprises at least one nonionic block copolymer surfactant, preferably, the nonionic block copolymer surfactant is selected from one or more poloxamers.

[0507] Numbered implementation plan 7

[0508] The use according to any one of numbered embodiments 1 to 6, wherein the sulfur-containing compound is selected from the group consisting of sulfone-containing compounds, sulfate-containing compounds, and sulfonate-containing compounds.

[0509] Numbered implementation scheme 8

[0510] The use according to numbered embodiment 7, wherein the sulfur-containing compound comprises 1,3-propylene glycol cyclic sulfate (PCS).

[0511] Numbered implementation scheme 9

[0512] The use according to any one of numbered embodiments 1 to 8, wherein the boron-containing compound is selected from a borate-containing ester compound and a boroxine-containing compound.

[0513] Numbered implementation scheme 10

[0514] The use according to numbered embodiment 9, wherein the boron-containing compound comprises tris(trimethylsilyl)borate (TMSB).

[0515] Numbered implementation plan 11

[0516] The use according to any of numbered embodiments 1 to 10, wherein the first component comprises triethyl phosphate in an amount of about 90% or more by weight of the first component of the solvent system.

[0517] Numbered implementation scheme 12

[0518] The use according to any one of numbered embodiments 1 to 11 in an electrochemical cell, preferably a sodium based electrochemical cell.

[0519] Numbered implementation plan 13

[0520] The use according to numbered embodiment 12, wherein the electrochemical cell is a metal ion battery comprising a negative electrode and a positive electrode.

[0521] Numbered implementation scheme 14

[0522] The use according to numbered embodiment 13, wherein the metal ion battery is selected from sodium ion batteries, lithium ion batteries and potassium ion batteries.

[0523] Numbered implementation plan 15

[0524] The use according to numbered embodiment 12, wherein the electrochemical cell is an anode-free sodium cell.

[0525] Numbered implementation plan 16

[0526] The use according to any one of numbered embodiments 1 to 15 in an electrochemical cell associated with or integrated with one or more further electrochemical cells having one or more metal-containing salts in a concentration greater than 0.2 mol / kg.

[0527] Numbered implementation plan 17

[0528] A method of obtaining usable energy from an electrochemical cell, the method comprising:

[0529] An electrochemical cell is operated using an electrolyte composition comprising a solvent system comprising:

[0530] A first component comprising one or more non-aqueous solvents;

[0531] a second component comprising one or more performance additives selected from the group consisting of sulfur-containing compounds, boron-containing compounds, and surfactants; and

[0532] Wherein, the electrolyte composition further comprises one or more metal-containing salts in a concentration of 0 mol / kg to ≤0.2 mol / kg.

[0533] Numbered implementation plan 18

[0534] A method according to numbered embodiment 17, further comprising associating or integrating the usable energy from the electrochemical cell with one or more additional electrochemical cells having one or more metal-containing salts at a concentration greater than 0.2 mol / kg.

[0535] Numbered implementation plan 19

[0536] A method of making an electrochemical cell, the method comprising:

[0537] An electrolyte composition comprising a solvent system is introduced into an electrochemical cell, the solvent system comprising:

[0538] A first component comprising one or more non-aqueous solvents;

[0539] a second component comprising one or more performance additives selected from the group consisting of sulfur-containing compounds, boron-containing compounds, and surfactants; and

[0540] Wherein, the electrolyte composition further comprises one or more metal-containing salts in a concentration of 0 mol / kg to ≤0.2 mol / kg.

[0541] Numbered implementation plan 20

[0542] The method of any of numbered embodiments 17 to 19, wherein the electrolyte composition is substantially free of one or more metal-containing salts.

[0543] Numbered implementation plan 21

[0544] The method of any one of numbered embodiments 17 to 20, wherein the one or more non-aqueous solvents are selected from organic phosphate-based solvents, organic carbonate-based solvents, and glyme-based solvents.

[0545] Numbered implementation plan 22

[0546] The method of any of numbered embodiments 17 to 21, wherein the second component comprises one or more performance additives in an amount of >0.5% to ≤10% by weight of the solvent system.

[0547] Numbered implementation plan 23

[0548] The method of any one of numbered embodiments 17 to 22, wherein the surfactant is selected from anionic surfactants, cationic surfactants, nonionic (hydrophilic) surfactants, and amphoteric (zwitterionic) surfactants.

[0549] Numbered implementation plan 24

[0550] The method according to any one of numbered embodiments 17 to 23, wherein the surfactant comprises at least one nonionic block copolymer surfactant, preferably the nonionic block copolymer surfactant is selected from one or more poloxamers.

[0551] Numbered implementation plan 25

[0552] The method of any one of numbered embodiments 17 to 24, wherein the sulfur-containing compound is selected from the group consisting of sulfone-containing compounds, sulfate-containing compounds, and sulfonate-containing compounds.

[0553] Numbered implementation 26

[0554] The method according to numbered embodiment 25, wherein the sulfur-containing compound comprises 1,3-propylene glycol cyclic sulfate (PCS).

[0555] Numbered implementation plan 27

[0556] The method of any one of numbered embodiments 17 to 26, wherein the boron-containing compound is selected from a borate-containing ester compound and a boroxine-containing compound.

[0557] Numbered implementation plan 28

[0558] The method of numbered embodiment 27, wherein the boron-containing compound comprises tris(trimethylsilyl)borate (TMSB).

[0559] Numbered implementation plan 29

[0560] The method of any one of numbered embodiments 17 to 28, wherein the first component comprises triethyl phosphate in an amount of about 90% or more by weight of the first component of the solvent system.

[0561] Numbered implementation plan 30

[0562] The method of any one of numbered embodiments 17 to 29, wherein the electrochemical cell is a sodium-based electrochemical cell.

[0563] Numbered implementation plan 31

[0564] The method of any one of numbered embodiments 17 to 29, wherein the electrochemical cell is a metal ion battery comprising a negative electrode and a positive electrode.

[0565] Numbered implementation plan 32

[0566] A method according to numbered embodiment 31, wherein the metal ion battery is selected from a sodium ion battery, a lithium ion battery and a potassium ion battery.

[0567] Numbered implementation plan 33

[0568] The method of any one of numbered embodiments 17 to 29, wherein the electrochemical cell is an anode-free sodium cell.

[0569] Numbered implementation plan 34

[0570] An electrochemical cell prepared by the method according to any one of numbered embodiments 19 to 33.

[0571] Numbered implementation plan 35

[0572] An electrochemical cell having an electrolyte composition comprising a solvent system comprising:

[0573] A first component comprising one or more non-aqueous solvents;

[0574] a second component comprising one or more performance additives selected from the group consisting of sulfur-containing compounds, boron-containing compounds, and surfactants; and

[0575] Wherein, the electrolyte composition further comprises one or more metal-containing salts in a concentration of 0 mol / kg to ≤0.2 mol / kg.

[0576] Numbered implementation plan 36

[0577] An electrochemical cell according to numbered embodiment 35, wherein the electrolyte composition is substantially free of one or more metal-containing salts.

[0578] Numbered implementation plan 37

[0579] The electrochemical cell of any of numbered embodiments 35 to 36, wherein the one or more non-aqueous solvents are selected from organic phosphate-based solvents, organic carbonate-based solvents, and glyme-based solvents.

[0580] Numbered implementation plan 38

[0581] The electrochemical cell of any of numbered embodiments 35 to 37, wherein the second component comprises one or more performance additives in an amount of >0.5% to ≤10% by weight of the solvent system.

[0582] Numbered implementation plan 39

[0583] The electrochemical cell of any one of numbered embodiments 35 to 38, wherein the surfactant is selected from anionic surfactants, cationic surfactants, nonionic (hydrophilic) surfactants, and amphoteric (zwitterionic) surfactants.

[0584] Numbered implementation scheme 40

[0585] The electrochemical cell according to numbered embodiment 39, wherein the surfactant comprises at least one non-ionic block copolymer surfactant, preferably, the non-ionic block copolymer surfactant is selected from one or more poloxamers.

[0586] Numbered implementation scheme 41

[0587] The electrochemical cell of any of numbered embodiments 35 to 40, wherein the sulfur-containing compound is selected from the group consisting of sulfone-containing compounds, sulfate-containing compounds, and sulfonate-containing compounds.

[0588] Numbered implementation scheme 42

[0589] The electrochemical cell of numbered embodiment 41, wherein the sulfur-containing compound comprises 1,3-propylene glycol cyclic sulfate (PCS).

[0590] Numbered implementation scheme 43

[0591] The electrochemical cell of any of numbered embodiments 35 to 42, wherein the boron-containing compound is selected from a borate-containing ester compound and a boroxine-containing compound.

[0592] Numbered implementation scheme 44

[0593] The electrochemical cell of numbered embodiment 43, wherein the boron-containing compound comprises tris(trimethylsilyl)borate (TMSB).

[0594] Numbered implementation plan 45

[0595] The electrochemical cell of any one of numbered embodiments 35 to 44, wherein the first component comprises triethyl phosphate in an amount of about 90% or more by weight of the first component of the solvent system.

[0596] Numbered implementation scheme 46

[0597] The electrochemical cell of any one of numbered embodiments 35 to 45, wherein the electrochemical cell is a sodium-based electrochemical cell.

[0598] Numbered implementation scheme 47

[0599] The electrochemical cell of any one of numbered embodiments 35 to 45, wherein the electrochemical cell is a metal ion battery comprising a negative electrode and a positive electrode.

[0600] Numbered implementation scheme 48

[0601] An electrochemical cell according to numbered embodiment 47, wherein the metal ion battery is selected from a sodium ion battery, a lithium ion battery and a potassium ion battery.

[0602] Numbered implementation scheme 49

[0603] The electrochemical cell of any one of numbered embodiments 35 to 45, wherein the electrochemical cell is an anode-free sodium cell.

[0604] Numbered implementation plan 50

[0605] A device comprising an electrochemical cell according to any one of numbered embodiments 35 to 49.

[0606] Numbered implementation plan 51

[0607] The device according to numbered embodiment 50, wherein the device also includes one or more electrochemical cells, wherein the one or more electrochemical cells have an electrolyte composition, and the electrolyte composition comprises one or more metal salts at a concentration greater than 0.2 mol / kg.

Claims

1. Use of a composition comprising a solvent system as an electrolyte, the solvent system comprising: A first component comprising one or more non-aqueous solvents; a second component comprising one or more performance additives selected from the group consisting of sulfur-containing compounds, boron-containing compounds, and surfactants; and The composition further comprises one or more metal-containing salts at a concentration of 0 mol / kg to ≤0.2 mol / kg.

2. The use according to claim 1, wherein the composition is substantially free of one or more metal-containing salts.

3. The use according to claim 1 or claim 2, wherein the one or more non-aqueous solvents are selected from organic phosphate-based solvents, organic carbonate-based solvents and glyme-based solvents.

4. Use according to any one of claims 1 to 3, wherein the second component comprises one or more performance additives in an amount of >0.5% to ≤10% by weight of the solvent system.

5. Use according to any one of claims 1 to 4, wherein the surfactant is selected from anionic surfactants, cationic surfactants, nonionic (hydrophilic) surfactants and amphoteric (zwitterionic) surfactants.

6. The use according to claim 5, wherein the surfactant comprises at least one nonionic block copolymer surfactant, preferably, the nonionic block copolymer surfactant is selected from one or more poloxamers.

7. The use according to any one of claims 1 to 6, wherein the sulfur-containing compound is selected from the group consisting of a sulfone-containing compound, a sulfate-containing compound and a sulfonate-containing compound.

8. The use according to claim 7, wherein the sulfur-containing compound comprises 1,3-propylene glycol cyclic sulfate (PCS).

9. The use according to any one of claims 1 to 8, wherein the boron-containing compound is selected from a borate-containing ester compound and a boroxine-containing compound.

10. The use according to claim 9, wherein the boron-containing compound comprises tris(trimethylsilyl)borate (TMSB).

11. The use according to any one of claims 1 to 10, wherein the first component comprises triethyl phosphate in an amount of about 90% or more by weight of the first component of the solvent system.

12. Use according to any one of claims 1 to 11 in an electrochemical cell, preferably in a sodium-based electrochemical cell.

13. Use according to claim 12, wherein the electrochemical cell is a metal ion battery comprising a negative electrode and a positive electrode.

14. The use according to claim 13, wherein the metal ion battery is selected from a sodium ion battery, a lithium ion battery and a potassium ion battery.

15. The use according to claim 12, wherein the electrochemical cell is an anode-free sodium cell.

16. Use according to any one of claims 1 to 15, for an electrochemical cell associated with or integrated with one or more further electrochemical cells having one or more metal-containing salts in a concentration greater than 0.2 mol / kg.

17. A method of obtaining usable energy from an electrochemical cell, the method comprising: The electrochemical cell is operated using an electrolyte composition comprising a solvent system comprising: A first component comprising one or more non-aqueous solvents; a second component comprising one or more performance additives selected from the group consisting of sulfur-containing compounds, boron-containing compounds, and surfactants; and Wherein, the electrolyte composition further comprises one or more metal-containing salts in a concentration of 0 mol / kg to ≤0.2 mol / kg.

18. The method of claim 17, comprising cycling the electrochemical cell at a C-rate of about C / ≥2.

19. A method of making an electrochemical cell, the method comprising: An electrolyte composition comprising a solvent system is introduced into an electrochemical cell, the solvent system comprising: A first component comprising one or more non-aqueous solvents; a second component comprising one or more performance additives selected from the group consisting of sulfur-containing compounds, boron-containing compounds, and surfactants; and Wherein, the electrolyte composition further comprises one or more metal-containing salts in a concentration of 0 mol / kg to ≤0.2 mol / kg.

20. An electrochemical cell having an electrolyte composition comprising a solvent system comprising: A first component comprising one or more non-aqueous solvents; a second component comprising one or more performance additives selected from the group consisting of sulfur-containing compounds, boron-containing compounds, and surfactants; and in, The electrolyte composition further comprises one or more metal-containing salts at a concentration of 0 mol / kg to ≤ 0.2 mol / kg.

21. A device comprising the electrochemical cell according to claim 20.

22. An electrolyte composition comprising a solvent system, wherein the solvent system comprises: A first component comprising one or more non-aqueous solvents; a second component comprising one or more performance additives including a sulfur-containing compound; and in, The electrolyte composition further comprises one or more metal-containing salts at a concentration of 0 mol / kg to ≤ 0.2 mol / kg.

23. An electrolyte composition comprising a solvent system, wherein the solvent system comprises: A first component comprising one or more non-aqueous solvents; A second component comprising one or more performance additives selected from boron-containing compounds and surfactants in an amount of >0.5% to ≤10% by weight of the solvent system; and wherein the electrolyte composition further comprises one or more metal-containing salts in a concentration of 0 mol / kg to ≤0.2 mol / kg.

Citation Information

Patent Citations

  • Non-aqueous electrolyte compositions

    WO2020240209A1

Cited By

  • Perovskite flexible solar battery and lithium-sulfur battery integrated self-charging system and preparation thereof

    CN115911619A